Assessing safe operating tubes for managing social-ecological systems using controllability, reachability and viability concepts - Jean-Denis Mathias; John M. Anderies (Ecological Modelling, 2026)

Temperate Forest Floors: Ecosystem Hubs in Transition? - Friederike Lang; Jörg Prietzel; Frank Hagedorn; Klaus Kaiser; Stefanie Schulz; Mathias Mayer; Lars Vesterdal; Jürgen Bauhus; Maï Bergmann; Sebastian Bibinger; Martin I. Bidartondo; Jingxuan Olivia Chen; et al. (Global Change Biology, 2026)
The forest floor (FF) plays a key role in carbon, nutrient, and water cycling. It is the biologically most active compartment of forest soils, highly responsive to environmental conditions. Yet, its response to current changes in environmental conditions and forest management is understudied. Temperate forests are among the best studied ecosystems globally, providing the necessary ecological and biogeochemical background information to assess FF changes. Here, we focus on identifying existing knowledge and gaps in our understanding of the functioning of the FF. Interactions between FF biota and abiotic FF components show multifactorial dependencies with environmental conditions and drive FF turnover. Vice versa, the turnover of FF regulates carbon, nutrient, and water cycling. With slow litter decomposition and limited bioturbation, organic matter accumulates, nutrients cycle tightly within the FF, and water passes through this layer partly along preferential pathways. With rapid litter decomposition and intense bioturbation, FF accumulation is little, the mineral soil is the main nexus for plant nutrient uptake and organic matter transformation, and water infiltrates the mineral soil more homogeneously. The interconnectedness with the adjacent ecosystem compartments is a crucial feature of the FF, feeding back to its functioning and making it a central hub of forest processes. The FF morphology reflects these processes and therefore has untapped potential as an indicator of soil and ecosystem health. Under forest change, the FF might lose its functionality, with negative impacts on nutrient provision, water storage, and carbon sequestration. Consequences for forest growth could be strong and even detrimental. Hence, improved knowledge of FF characteristics and their linkages to mineral soils and aboveground ecosystem compartments is crucial for assessing forest resilience to progressing environmental changes.

Land use, flooding regime, and seasons differentially shape composition of beetle species in a semi-arid highland floodplain in Central Kenya - Jane M. Macharia; Mathias Becker; Helida Oyieke; Kai Behn (International Journal of Tropical Insect Science, 2026)
Biodiversity is threatened globally by human-mediated alteration of natural environment. This includes East African wetland ecosystems that are subject to agriculture expansion and intensification. Monitoring of biodiversity is crucial to understand and mitigate biodiversity losses. Beetles, while rarely studied, are potentially useful bioindicators due to their sensitivity to environmental changes. Our study aimed at investigating the influence of land use regimes (cropland, fallow, grazing land, pristine), as well as flooding regimes and seasonality on the abundance, composition, diversity, and occurrence of beetle species in the Ewaso Narok swamp, Kenya. Using pitfall traps and sweep nets over two years (2015–2016) in 42 plots each of six sampling dates, we recorded 2,145 beetles (20 families, 179 species). Conversely to our hypothesis, we only found weak effects of land use on abundance, diversity and species composition. Seasons, and individual sampling dates were more important, partly due to varying rainfall prior to the sampling. Heavy rainfall decreased abundance of ground-dwelling beetles, particularly in the wettest zone. Regarding individual species, most occurred across all land uses and did not show much specificity. However, among ground-dwelling beetles, some species demonstrated significant associations with land use intensity. For instance, disturbance tolerant Tenebrionids such as Zophosis abyssinica and Gonocephalum simplex were associated with high land use intensity (cropland/fallows), while predatory Staphylinid Philonthus circumcinctus was associated with grazing lands. Hence, selected species may act as bioindicators and may represent “winners” and “losers” of land transformations. These results support biodiversity monitoring and future wetland use planning.

Structure elucidation of leadbeaterin-1, an ichthyotoxin associated with fish-killing blooms of Chrysochromulina leadbeateri in Northern Norwegian fjords - Xinhui Wang; Anita Solhaug; Bruno C. Garrido; Elizabeth M. Mudge; Mathias Fon; Aaron J.C. Andersen; Ingunn A. Samdal; Bente Edvardsen; Charlotte H. Gotfredsen; Per Juel Hansen; Christopher O. Miles; Thomas O. Larsen (Harmful Algae, 2026)

Hydrogeochemical and isotopic characterization of the upper and intermediate aquifers of the casamance (Senegal) - Mouhamet M. Diaw; Isai Bassène; Ibra D. Gueye; Djim M. L. Diongue; Mathias Diedhiou; Rim Trabelsi; Kamel Zouari; Serigne Faye (Environmental Geochemistry and Health, 2026)

Indoor airborne bacterial communities and adult lung health: A cross-sectional study - Hesham Amin; Christine Cramer; Kai Finster; Francisco Gomez Real; Thorarinn Gislason; Mathias Holm; Christer Janson; Nils Oskar Jögi; Rain Jogi; Andrei Malinovschi; Lars Modig; Dan Norbäck; et al. (International Journal of Hygiene and Environmental Health, 2026)

Bioenergetic trophic trade‐offs determine mass‐dependent extinction thresholds across the Cenozoic - Justin D. Yeakel; Matthew C. Hutchinson; Christopher P. Kempes; Paul L. Koch; Pedro D. S. Ugarte; Jacquelyn L. Gill; Mathias M. Pires (Ecology, 2026)
Body size constrains trophic interactions, shaping the feasibility of species' populations. Over macroevolutionary timescales, these constraints feed back to shape selection on body size and diet. We develop a bioenergetic, three‐level trophic framework—typical of terrestrial mammalian ecosystems—to explore how bioenergetic trade‐offs emerging from predator–prey interactions constrain coexistence. We show that interactions among predators, prey, and subsidies destabilize populations at both small and large sizes, matching observed limits to predator size and diet. These instabilities constrain coexistence and highlight a feasible predator size range of ca. 40–110 kg, spanning the mean size of terrestrial Cenozoic hypercarnivores. Finally, we show that decreased dietary selectivity confers a fitness advantage to larger carnivores that wanes at the largest sizes, aligning with diet estimates for contemporary and Pleistocene species. Our results underscore that ecological pressures emerging from trophic interactions, rooted in energetics, give rise to selective forces driving observed macroevolutionary patterns.

Biodiversity and spatial variation of subtidal rocky bottom communities in the west section of the Magellan Strait, Chile - Benjamín Rodríguez-Stepke; Ingrid M. Espinosa-León; Lorena A. Valenzuela-Lobos; Ana De La Torriente; Mathias Hüne (Marine Biology Research, 2026)

Fire and edge disturbances in the Amazon rainforest: impacts on animal–fruit and seed interactions - Jefferson Bruno B. S. Oliveira; Wesley Dáttilo; Hernani F. M. Oliveira; Paulo M. Brando; Walter S. de Araújo; Mathias M. Pires; Lucas N. Paolucci (Oecologia, 2026)
Burned forests—particularly at their edges—are expected to lose capacity for regeneration, and subsequent disturbances may further limit it. Animal–plant interactions are critical to the resilience of tropical forests to disturbances, as they sustain key ecological functions. However, climate and land-use changes are intensifying fire regimes, potentially disrupting these interactions. Using experimental approaches with artificial fruits (in the understory and on the terrestrial level) and agricultural crop seeds (accessed by all fauna and invertebrates-only), we investigated how animal–plant interactions, focusing on key faunal groups, are affected in disturbed forests 12 years after repeated experimental fires and under continuous edge effects in the southeastern Brazilian Amazon. We found that understory animal–fruit interactions were similar across burned, edge, and undisturbed forests, whereas terrestrial animal–fruit interactions were twice as high at the unburned edge. While vertebrates accessed understory fruits more frequently, invertebrates dominated terrestrial interactions, highlighting their complementary roles. In contrast, seed interactions by both the broader faunal community and invertebrates-only declined in the interior and edge of burned forests, while invertebrate-driven seed interactions were similar between unburned edge and burned forest interior. Our findings show contrasting responses to indirect fire and edge effects across ecological interactions that support forest regeneration. Therefore, we underscore the fragility of ecological interactions through faunal access to reproductive vegetation diaspores: while animal–fruit interactions were resilient in burned forests and edges, secondary animal–seed interactions were impacted by fire. These results suggest that disturbed forests may require more than a decade to recover their interactions fully.

A Review of Phage Therapy for Aquaculture Applications: Efficacy, Health Ramifications and Research Challenges - Louise James; Tamsyn M. Uren Webster; Gethin Thomas; Mathias Middelboe; Sofia Consuegra (Fish and Fisheries, 2026)
The emergence of antimicrobial resistance has encouraged a reappraisal of bacteriophage therapy for the mitigation of bacterial diseases in different environmental settings, including aquaculture. Here, we review aquaculture applications of phage therapy by considering its efficacy and potential for broader host‐associated effects, including host immunity, microbiome composition and behaviour. The advantages of phage therapy for aquaculture include the natural abundance and diversity of phages in water, and their self‐propagation, host specificity, low environmental impact and diverse administration routes. Although the efficacy of phage therapy in controlling the prevalence of bacterial pathogens across various aquaculture species is well demonstrated, the diversity of phage administration methods, experimental conditions, target strains and host physiologies have prevented a clear consensus being reached regarding the suitability of phage therapy for aquaculture. The application of phage therapy as an antimicrobial strategy induces gentler immune modulation compared to antibiotics and disinfectants, which often induce dysbiosis in host microbiomes by eliminating beneficial or commensal bacteria. However, there are divergent results regarding the influence of phage administration upon host microbiome composition and dynamics, with potentially important health implications that require further research. How phage immunogenicity may influence the host immune response is also unclear. Additional concerns include phage‐neutralising antibody production, phage‐resistant bacteria and horizontal gene transfer of antimicrobial resistance. Together, these represent areas warranting further research in aquaculture, along with the development of suitable fish models that demonstrate the broad applicability of phage therapy across multiple species.

Taphonomic signature of benthic foraminifera linked to methane release in the Barents Sea - Gabriella M. Boretto; Mathia Sabino; Fiorenza Torricella; Gianmarco Ingrosso; Alessio Nogarotto; Giuliana Panieri; Jens Hefter; Gesine Mollenhauer; Leonardo Langone; Silvia Giuliani; Tommaso Tesi; Lucilla Capotondi (Marine Geology, 2026)

Developing a cost and time efficient strategy for assessing novel materials for wastewater treatment with non-target screening analysis - Alba Rodriguez-Otero; Selina Tisler; Lisa M. Reinhardt; Mathias B. Jørgensen; David I. Pattison; Brice Bouyssiere; Jan H. Christensen (Journal of Hazardous Materials, 2026)

Beyond Climate Change: The Role of Integrated Soil Fertility Management for Sustaining Future Maize Yield in Sub‐Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Johan Six; Moritz Laub; Alex C. Ruane; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; et al. (Global Change Biology, 2026)
Climate change is projected to exacerbate food insecurity in sub‐Saharan Africa (SSA) by reducing crop yields and soil fertility. Many climate change impact studies in SSA have overlooked long‐term effects of soil fertility on crop yield. We evaluated maize yields under different scenarios of soil fertility (using soil organic carbon as a proxy) and climate change (considering changes in temperature, rainfall, and CO 2 ) at four sites in SSA. Using an ensemble of 15 calibrated soil‐crop models, we found a strong consensus that, without fertilization, soil fertility declines over time, impacting maize yields more strongly than changes in temperature, rainfall, or CO 2 . The model ensemble indicated that when accounting for soil fertility changes, the yield benefits of combined application of organic and mineral inputs increase over time, even under climate change. These findings highlight the importance of considering long‐term change in soil fertility when assessing impacts of climate change and integrated nutrient management on crop production in SSA.

Bidirectional Effects of Sleep Deprivation Associated with Parkinson’s Disease on Behavior, Oxidative Stress, and Energy Metabolism in Male and Female Rats - Gisiane B. Mathia; Gabriel S. Mondo; Lucas C. Pedro; Flávia S. Niero; Nátalli R. Rocha; Laisa N. Santos; Letícia M. Leonardo; Josimar G. Pereira; Carolina G. Alano; Isabela S. Lemos; Khiany Mathias; Anita Dal Bó Tiscoski; et al. (Molecular Neurobiology, 2026)

Structural diversity, tree species richness and biomass production in new forests on agricultural land - Yamina M. Rosas; Inger Kappel Schmidt; Torben Riis-Nielsen; Lars Vesterdal; Per Gundersen; David Bille Byriel; Mathias Just Justesen; Davide Barsotti; Sebastian Kepfer-Rojas (Remote Sensing of Environment, 2025)

Quantifying Hierarchical Conflicts in Homology Statements - Krister M. Swenson; Afif Elghraoui; Faramarz Valafar; Siavash Mirarab; Mathias Weller (Journal of Molecular Evolution, 2025)

Evolving to invade: Using geometric morphometrics to assess wing shape variation in the Antarctic non-native fly Trichocera maculipennis - Jordan Hernández-Martelo; Mathias Jabs; Tamara Contador; Sanghee Kim; Sook young Lee; Laura M. Pérez; Mónica Remedios-De-León; Enrique Morelli; Peter Convey; Hugo A. Benítez (Zoologischer Anzeiger, 2025)

Pressure-temperature-time deformation of an Ediacaran-Cambrian foreland fold-and-thrust belt: the Southern Espinhaço Front, Araçuaí Orogen - Henrique C. Joncew; Ginaldo A.C. Campanha; Melina C.B. Esteves; Frederico M. Faleiros; Leonardo E. Lagoeiro; Klaus Wemmer; Ruy A.C. Vasconcelos; Bruno V. Ribeiro; Mathias Hueck (Journal of Structural Geology, 2025)

Construction of a 3D trophoblast model and validation by triiodothyronine (T3) treatment - Mariana M. Lourenço; Bianca M. Gonçalves; Vinícius V. Peghinelli; Maria T. de Sibio; Ester M. Vieira; Helena P. Tilli; Paula B. Rocha; Regiane M.C. Olímpio; Igor C. Deprá; Lucas S. Mathias; Marna E. Sakalem; Carlos R. Padovani; et al. (Tissue and Cell, 2025)

Behaviour of the critical elements As, Bi, In, Sb, and Te during processing of a skarn ore: A case study of the Ruwai Zn-Pb-Ag Deposit, Central Kalimantan, Indonesia - Shelly M. Faizy; Doreen Ebert; Alkis Kontonikas-Charos; Mathias Burisch; Arifudin Idrus; Ernowo Ernowo; Anggara Widyastanto; Max Frenzel (Minerals Engineering, 2025)

Submarine groundwater discharge into a temperate tidal basin: Mapping and characterization by a multi-method and multi-scale approach - Ercan Erkul; Tina Wunderlich; Dennis Wilken; Jan Igel; Mike Müller-Petke; Mathias Ronczka; Tobias Splith; Simon Fischer; Benjamin Gilfedder; Michael Ernst Böttcher; Cátia M. Ehlert von Ahn; Ralf Gründling; et al. (Estuarine, Coastal and Shelf Science, 2025)

Landscape-scale forest cover shapes the complexity of seed-dispersal networks in regenerating forest fragments - Robert Timmers; Marina C. Côrtes; Marijke van Kuijk; Guilherme G. Canassa; Romano Staneke; Fabiana S.O. Rosin; Maud P.J. van Hooff; Jorn J.H. Knuit; Mathias M. Pires; Merel B. Soons (Biological Conservation, 2025)

Improving current forecast by Leveraging Measured Data and numerical models via LiESNs - Felipe M. Moreno; Marcel R. de Barros; Artur Jordão; Marlon S. Mathias; Marcelo Dottori; Anna H. Reali Costa; Edson S. Gomi; Fabio G. Cozman; Eduardo A. Tannuri (Environmental Modelling & Software, 2025)

Wind-powered reservoir management with application to robust multi-objective optimization - Mathias M. Nilsen; Rolf J. Lorentzen; Andreas S. Stordal; Olwijn Leeuwenburgh; Eduardo Barros (Computational Geosciences, 2025)
This paper addresses the challenge of incorporating offshore wind power into reservoir management. Traditionally, oil and gas production is powered by gas turbines. While stable, gas turbines are a major source of CO2 emissions. In contrast, wind power produces power with minimal emissions. However, due to its high variability and uncertainty, including it in the optimization of operational strategies over extended periods can be challenging. In this paper, the optimization of production strategies over an ensemble of realistic wind power series is investigated. The ensemble is generated by a mathematical model consisting of an autoregressive model with a seasonal trend. The model is conditioned on relevant wind speed data from the North Sea with Bayesian inference. The wind speed data is selected from the open-access NORA10EI dataset. The methodology developed in this paper is applied to a multi-objective optimization problem, focusing on studying the tradeoff between profit and emissions. A benchmark test reservoir model and a detailed CO2 emissions calculator are employed. In this scenario, wind power is combined with traditional gas power, and all results are compared with a reference where only gas power is used. The experiment indicates that it is not possible to reduce emissions by 40% without the use of wind power.

A Review of Abrupt Permafrost Thaw: Definitions, Usage, and a Proposed Conceptual Framework - Hailey Webb; Matthias Fuchs; Benjamin W. Abbott; Thomas A. Douglas; Clayton D. Elder; Jessica Gilman Ernakovich; Eugenie S. Euskirchen; Mathias Göckede; Guido Grosse; Gustaf Hugelius; Miriam C. Jones; Charles Koven; et al. (Current Climate Change Reports, 2025)
Purpose of Review We review how ‘abrupt thaw’ has been used in published studies, compare these definitions to abrupt processes in other Earth science disciplines, and provide a definitive framework for how abrupt thaw should be used in the context of permafrost science. Recent Findings We address several aspects of permafrost systems necessary for abrupt thaw to occur and propose a framework for classifying permafrost processes as abrupt thaw in the future. Based on a literature review and our collective expertise, we propose that abrupt thaw refers to thaw processes that lead to a substantial persistent environmental change within a few decades. Abrupt thaw typically occurs in ice-rich permafrost but may be initiated in ice-poor permafrost by external factors such as hydrologic change (i.e., increased streamflow, soil moisture fluctuations, altered groundwater recharge) or wildfire. Summary Permafrost thaw alters greenhouse gas emissions, soil and vegetation properties, and hydrologic flow, threatening infrastructure and the cultures and livelihoods of northern communities. The term ‘abrupt thaw’ has emerged in scientific discourse over the past two decades to differentiate processes that rapidly impact large depths of permafrost, such as thermokarst, from more gradual, top-down thaw processes that impact centimeters of near-surface permafrost over years to decades. However, there has been no formal definition for abrupt thaw and its use in the scientific literature has varied considerably. Our standardized definition of abrupt thaw offers a path forward to better understand drivers and patterns of abrupt thaw and its consequences for global greenhouse gas budgets, impacts to infrastructure and land-use, and Arctic policy- and decision-making.

Associations of parental air pollution and greenness exposures with offspring asthma outcomes - Robin M. Sinsamala; Alessandro Marcon; Randi J. Bertelsen; Simone Accordini; Jørgen Brandt; Lise M. Frohn; Camilla Geels; Thorarinn Gislason; Mathias Holm; Christer Janson; Andrei Malinovschi; Iana Markevych; et al. (Environmental Research, 2025)

Reliable methodology to determine biotransformation of PBAT in anaerobic conditions - Alba Trueba-Santiso; Reinhard Wimmer; Mathias Eskildsen; Juan Cubero-Cardoso; Juan M. Lema; Jeppe Lund Nielsen (Bioresource Technology, 2025)

The Rise (and Fall?) of European Water Shrews: Phylogeography and Species Distribution Models Uncover the Impact of Climate Change - T. Neves; J. T. Tapisso; S. I. Gabriel; L. Rychlik; M. G. Ramalhinho; L. Borda‐de‐Água; A. Mishta; M. L. Mathias (Journal of Biogeography, 2025)
Aim Predicting the effects of climate change on species distributions, while considering their genetic differentiation and evolutionary history is crucial to develop conservation measures. Here we aim to: assess the phylogenetic and phylogeographical relationships between the European Neomys species and respective lineages; infer the demographic history of all genetic lineages and estimate the potential impact of future climate change on their distribution and persistence of the genetic lineages. Location Europe. Time Period The demographic analysis ranges from 350,000 ago to the present. The future climate change scenarios modelling ranges from the present to 2100. Major Taxa Studies Three species belonging to the genus Neomys . Methods We reconstructed the phylogenetic relationships between the species in Europe and unveiled their demographic history based on cytochrome b gene sequences while using presence data to model how their distribution might change under distinct climate change scenarios. Results Our results confirm the existence of a distinct N. milleri lineage in the Italian Peninsula, whose population size has been relatively constant over time. Except for this lineage, all species' populations have likely been increasing until at least 25,000 years ago. While our future projections are beneficial to N. milleri , relatively inconsequential to N. fodiens , but suggest the likely extinction of N. anomalus , endemic to the Iberian Peninsula and the Italian lineage of N. milleri . Main Conclusions The Mediterranean Peninsulas, acting as refugia from the extreme cold conditions during the Last Glacial Period, contributed to the genetic differentiation of N. anomalus and the Italian lineage of N. milleri . However, as climate warms, the Peninsulas will no longer be able to sustain these species/lineages. Given the Peninsulas' status as biodiversity hotspots, this vulnerability of their ecosystems to climate change should mobilise conservation efforts guided by phylogeographic approaches, allowing us to uncover putative lineages or endemisms before their potential extinction.

Combined engine configuration and speed optimization for fuel savings on cruise ships - Arash Marashian; Jari M. Böling; Abolhassan Razminia; Jari Hyvönen; Roberto Vettor; Wilhelm Gustafsson; Mathias Pirttikangas; Jerker Björkqvist (Ocean Engineering, 2025)

The impact of leaf-wood separation algorithms on aboveground biomass estimation from terrestrial laser scanning - Shilin Chen; Hans Verbeeck; Louise Terryn; Wouter A.J. Van den Broeck; Matheus Boni Vicari; Mathias Disney; Niall Origo; Di Wang; Zhouxin Xi; Chris Hopkinson; Wenxia Dai; Meilian Wang; et al. (Remote Sensing of Environment, 2025)

Umbrella, keystone, or flagship? An integrated framework for identifying effective surrogate species - Minyi Kau; Byron V. Weckworth; Sheng Li; Mathias M. Pires; Daiying Jin; Michela Pacifici; Carlo Rondinini; Luigi Boitani; Thomas M. McCarthy; Zhi Lu; George B. Schaller; Steven R. Beissinger; et al. (Biological Conservation, 2025)

Simulated isotopic fingerprint of the Atlantic Multidecadal Oscillation over South America and its relation to the Little Ice Age - Jelena Maksic; Marília Harumi Shimizu; Gilvan Sampaio; Cristiano M. Chiessi; Matthias Prange; Mathias Vuille; Giselle Utida; Francisco W. Cruz; Murilo Ruv Lemes (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Using the ODD protocol and NetLogo to replicate agent-based models - Volker Grimm; Uta Berger; Justin M. Calabrese; Ainara Cortés-Avizanda; Jordi Ferrer; Mathias Franz; Jürgen Groeneveld; Florian Hartig; Oliver Jakoby; Roger Jovani; Stephanie Kramer-Schadt; Tamara Münkemüller; et al. (Ecological Modelling, 2025)

Transpiration and water use strategies of three economic tree species in a semi-arid afforestation region - Wenjie Wu; Yue Li; Kiril Manevski; Mathias Neumann Andersen; Bingcheng Si; Yongcai Lou; Hao Feng; Kadambot H. M. Siddique (European Journal of Forest Research, 2025)

Charge as a key physicochemical factor in adsorption of organic micropollutants from wastewater effluent by rice husk bio-silica - Alba Rodriguez-Otero; Selina Tisler; Lisa M. Reinhardt; Mathias B. Jørgensen; Brice Bouyssiere; Jan H. Christensen (Water Research, 2025)

Further evidence of biallelic NAV3 variants associated with recessive neurodevelopmental disorder with dysmorphism, developmental delay, intellectual disability, and behavioral abnormalities - Naseebullah Kakar; Selinda Mascarenhas; Asmat Ali; Azmatullah; Syed M. Ijlal Haider; Vaishnavi Ashok Badiger; Mobina Shadman Ghofrani; Nathalie Kruse; Sohana Nadeem Hashmi; Jelena Pozojevic; Saranya Balachandran; Mathias Toft; et al. (Human Genetics, 2025)
Neuron navigators (NAVs) are cytoskeleton-associated proteins well known for their role in axonal guidance, neuronal migration, and neurite growth necessary for neurodevelopment. Neuron navigator 3 (NAV3) is one of the three NAV proteins highly expressed in the embryonic and adult brain. However, the role of the NAV3 gene in human disease is not well-studied. Recently, five bi-allelic and three mono-allelic variants in NAV3 were reported in 12 individuals from eight unrelated families with neurodevelopmental disorder (NDD). Here, we report five patients from three unrelated consanguineous families segregating autosomal recessive NDD. Patients have symptoms of dysmorphism, intellectual disability, developmental delay, and behavioral abnormalities. Exome sequencing (ES) was performed on two affected individuals from one large family, and one affected individual from each of the other two families. ES revealed two homozygous nonsense c.6325C > T; p.(Gln2109Ter) and c.6577C > T; p.(Arg2193Ter) and a homozygous splice site (c.243 + 1G > T) variants in the NAV3 (NM_001024383.2). Analysis of single-cell sequencing datasets from embryonic and young adult human brains revealed that NAV3 is highly expressed in the excitatory neurons, inhibitory neurons, and microglia, consistent with its role in neurodevelopment. In conclusion, in this study, we further validate biallelic protein truncating variants in NAV3 as a cause of NDD, expanding the spectrum of pathogenic variants in this newly discovered NDD gene.

Soil Microbiome Inoculation for Resilient and Multifunctional New Forests in Post‐Agricultural Landscapes - Sofia I. F. Gomes; Per Gundersen; T. Martijn Bezemer; Davide Barsotti; Ludovica D'Imperio; Konstantinos Georgopoulos; Mathias Just Justesen; Karelle Rheault; Yamina M. Rosas; Inger Kappel Schmidt; Leho Tedersoo; Lars Vesterdal; et al. (Global Change Biology, 2025)
Afforestation is increasingly recognized as a critical strategy to restore ecosystems and enhance biodiversity on post‐agricultural landscapes. However, agricultural legacies, such as altered soil structure, nutrient imbalances, and depleted microbial diversity, can slow down forest establishment or cause ecosystems to deviate from expected successional trajectories. In this opinion paper, we explore the potential of soil inoculations as a tool to overcome these challenges by introducing beneficial microbial communities that can accelerate ecosystem recovery and forest development. Restoring soil biodiversity is a crucial aspect of this process that drives broader ecosystem functionality and resilience. We highlight the need to carefully consider the type and timing of inoculations and to ensure compatibility between the inoculum and recipient site characteristics to optimize the establishment of introduced species. While tree productivity is often a central focus of afforestation efforts, the restoration of soil biodiversity, which will also contribute to increased ecosystem‐level functions, should also be a priority for long‐term forest resilience. Agricultural legacies add complexities to the restoration process, creating unique challenges that need to be addressed in restoration planning. Thus, successful inoculation strategies require a thorough understanding of both donor and recipient site characteristics, also in relation to potential mismatches related to soil physiochemical properties to avoid unintended consequences such as the non‐establishment of introduced species. Additionally, we call for the re‐evaluation of afforestation targets and the development of standardized monitoring protocols that track the success of inoculation efforts, particularly regarding soil health, microbial community establishment, and biodiversity recovery. By integrating inoculation practices within a broader restoration framework, we can enhance the resilience, biodiversity, and ecosystem functionality of newly afforested landscapes. Ultimately, this approach may play a critical role in ensuring the success of large‐scale afforestation projects.

Manila clams Ruditapes philippinarum spreading north and establishing in the European Wadden Sea - Karsten Reise; K Mathias Wegner; Rainer Borcherding; Sarah Brand; Christian Buschbaum; Andreas M Waser (Estuarine, Coastal and Shelf Science, 2024)

Mixed effect estimation in deep compartment models: Variational methods outperform first-order approximations - Alexander Janssen; Frank C. Bennis; Marjon H. Cnossen; Ron A. A. Mathôt; S. H. Reitsma; F. W. G. Leebeek; M. Coppens; K. Fijnvandraat; K. Meijer; S. E. M. Schols; H. C. J. Eikenboom; R. E. G. Schutgens; et al. (Journal of Pharmacokinetics and Pharmacodynamics, 2024)
This work focusses on extending the deep compartment model (DCM) framework to the estimation of mixed-effects. By introducing random effects, model predictions can be personalized based on drug measurements, enabling the testing of different treatment schedules on an individual basis. The performance of classical first-order (FO and FOCE) and machine learning based variational inference (VI) algorithms were compared in a simulation study. In VI, posterior distributions of the random variables are approximated using variational distributions whose parameters can be directly optimized. We found that variational approximations estimated using the path derivative gradient estimator version of VI were highly accurate. Models fit on the simulated data set using the FO and VI objective functions gave similar results, with accurate predictions of both the population parameters and covariate effects. Contrastingly, models fit using FOCE depicted erratic behaviour during optimization, and resulting parameter estimates were inaccurate. Finally, we compared the performance of the methods on two real-world data sets of haemophilia A patients who received standard half-life factor VIII concentrates during prophylactic and perioperative settings. Again, models fit using FO and VI depicted similar results, although some models fit using FO presented divergent results. Again, models fit using FOCE were unstable. In conclusion, we show that mixed-effects estimation using the DCM is feasible. VI performs conditional estimation, which might lead to more accurate results in more complex models compared to the FO method.

Liveability in large housing estates in Germany – Identifying differences based on a novel concept for a walkable city - Manuel Köberl; Michael Wurm; Ariane Droin; Oana M. Garbasevschi; Mathias Dolls; Hannes Taubenböck (Landscape and Urban Planning, 2024)

Non-Gaussian Ensemble Optimization - Mathias M. Nilsen; Andreas S. Stordal; Patrick N. Raanes; Rolf J. Lorentzen; Kjersti S. Eikrem (Mathematical Geosciences, 2024)
Ensemble-based optimization (EnOpt), commonly used in reservoir management, can be seen as a special case of a natural evolution algorithm. Stein’s lemma gives a new interpretation of EnOpt. This interpretation enables us to study EnOpt in the context of general mutation distributions. In this paper, a non-Gaussian generalization of EnOpt (GenOpt) is proposed, where the control gradient is estimated using Stein’s lemma, and the mutation distribution is updated separately via natural evolution. For the multivariate case, a Gaussian copula is used to represent dependencies between the marginals. The correlation matrix is also iteratively optimized. It is shown that using beta distributions as marginals in the GenOpt algorithm addresses the truncation problem that sometimes arises when applying EnOpt on bounded optimization problems. The performance of the proposed optimization algorithm is evaluated on several test cases. The experiments indicate that GenOpt is less dependent on the chosen hyperparameters, and it is able to converge more quickly than EnOpt on a reservoir management test case.

Treatment with lipoxin A4 improves influenza A infection outcome, induces macrophage reprogramming, anti-inflammatory and pro-resolutive responses - Flavia Rago; Eliza Mathias Melo; Leigh M. Miller; Alexis M. Duray; Franciel Batista Felix; Juliana Priscila Vago; Ana Paula de Faria Gonçalves; Ana Luiza Pessoa Mendonça Angelo; Geovanni D. Cassali; Monica de Gaetano; Eoin Brennan; Benjamin Owen; et al. (Inflammation Research, 2024)

Elevated risk of adverse effects from foodborne contaminants and drugs in inflammatory bowel disease: a review - Tom Walraven; Mathias Busch; Jingxuan Wang; Joanne M. Donkers; Marjolijn Duijvestein; Evita van de Steeg; Nynke I. Kramer; Hans Bouwmeester (Archives of Toxicology, 2024)
The global burden of Inflammatory bowel disease (IBD) has been rising over the last decades. IBD is an intestinal disorder with a complex and largely unknown etiology. The disease is characterized by a chronically inflamed gastrointestinal tract, with intermittent phases of exacerbation and remission. This compromised intestinal barrier can contribute to, enhance, or even enable the toxicity of drugs, food-borne chemicals and particulate matter. This review discusses whether the rising prevalence of IBD in our society warrants the consideration of IBD patients as a specific population group in toxicological safety assessment. Various in vivo, ex vivo and in vitro models are discussed that can simulate hallmarks of IBD and may be used to study the effects of prevalent intestinal inflammation on the hazards of these various toxicants. In conclusion, risk assessments based on healthy individuals may not sufficiently cover IBD patient safety and it is suggested to consider this susceptible subgroup of the population in future toxicological assessments.

New tree height allometries derived from terrestrial laser scanning reveal substantial discrepancies with forest inventory methods in tropical rainforests - Louise Terryn; Kim Calders; Félicien Meunier; Marijn Bauters; Pascal Boeckx; Benjamin Brede; Andrew Burt; Jerome Chave; Antonio Carlos Lola da Costa; Barbara D'hont; Mathias Disney; Tommaso Jucker; et al. (Global Change Biology, 2024)
Tree allometric models, essential for monitoring and predicting terrestrial carbon stocks, are traditionally built on global databases with forest inventory measurements of stem diameter (D) and tree height (H). However, these databases often combine H measurements obtained through various measurement methods, each with distinct error patterns, affecting the resulting H:D allometries. In recent decades, terrestrial laser scanning (TLS) has emerged as a widely accepted method for accurate, non‐destructive tree structural measurements. This study used TLS data to evaluate the prediction accuracy of forest inventory‐based H:D allometries and to develop more accurate pantropical allometries. We considered 19 tropical rainforest plots across four continents. Eleven plots had forest inventory and RIEGL VZ‐400(i) TLS‐based D and H data, allowing accuracy assessment of local forest inventory‐based H:D allometries. Additionally, TLS‐based data from 1951 trees from all 19 plots were used to create new pantropical H:D allometries for tropical rainforests. Our findings reveal that in most plots, forest inventory‐based H:D allometries underestimated H compared with TLS‐based allometries. For 30‐metre‐tall trees, these underestimations varied from −1.6 m (−5.3%) to −7.5 m (−25.4%). In the Malaysian plot with trees reaching up to 77 m in height, the underestimation was as much as −31.7 m (−41.3%). We propose a TLS‐based pantropical H:D allometry, incorporating maximum climatological water deficit for site effects, with a mean uncertainty of 19.1% and a mean bias of −4.8%. While the mean uncertainty is roughly 2.3% greater than that of the Chave2014 model, this model demonstrates more consistent uncertainties across tree size and delivers less biased estimates of H (with a reduction of 8.23%). In summary, recognizing the errors in H measurements from forest inventory methods is vital, as they can propagate into the allometries they inform. This study underscores the potential of TLS for accurate H and D measurements in tropical rainforests, essential for refining tree allometries.

Do Tasmanian devil declines impact ecosystem function? - Torrey Stephenson; Tara Hudiburg; Justin M. Mathias; Menna Jones; Laurel M. Lynch (Global Change Biology, 2024)
Tasmanian eucalypt forests are among the most carbon‐dense in the world, but projected climate change could destabilize this critical carbon sink. While the impact of abiotic factors on forest ecosystem carbon dynamics have received considerable attention, biotic factors such as the input of animal scat are less understood. Tasmanian devils ( Sarcophilus harrisii )—an osteophageous scavenger that can ingest and solubilize nutrients locked in bone material—may subsidize plant and microbial productivity by concentrating bioavailable nutrients (e.g., nitrogen and phosphorus) in scat latrines. However, dramatic declines in devil population densities, driven by the spread of a transmissible cancer, may have underappreciated consequences for soil organic carbon (SOC) storage and forest productivity by altering nutrient cycling. Here, we fuse experimental data and modeling to quantify and predict future changes to forest productivity and SOC under various climate and scat‐quality futures. We find that devil scat significantly increases concentrations of nitrogen, ammonium, phosphorus, and phosphate in the soil and shifts soil microbial communities toward those dominated by r ‐selected (e.g., fast‐growing) phyla. Further, under expected increases in temperature and changes in precipitation, devil scat inputs are projected to increase above‐ and below‐ground net primary productivity and microbial biomass carbon through 2100. In contrast, when devil scat is replaced by lower‐quality scat (e.g., from non‐osteophageous scavengers and herbivores), forest carbon pools are likely to increase more slowly, or in some cases, decline. Together, our results suggest often overlooked biotic factors will interact with climate change to drive current and future carbon pool dynamics in Tasmanian forests.

Pan-African granitic magmatism of the Kaoko Belt: Tectonic perspective from its South American connection and insights into the crustal architecture of SW Gondwana - Mathias Hueck; Miguel A.S. Basei; Hartwig Frimmel; Lucas M. Lino; Vinicius X. Corrêa; Lucas R. Tesser; Mario C. Campos Neto; Carlos E. Ganade (Precambrian Research, 2024)

Africa Alive Corridors: Transdisciplinary Research based on African Footprints - B. Linol; M. Doucouré; J. Anderson; F. Toteu; W. Miller; P. Vale; P. Hoffman; G. I. H. Kerley; R. Auerbach; C. Thiart; M. Meghraoui; N. Dhliwayo; et al. (Geoheritage, 2024)
The idea of Africa Alive Corridors (AAC) evolved from Gondwana geological mapping to a comprehensive, more inclusive and dynamic approach to transdisciplinary research known as Earth Stewardship Science. Twenty designated corridors explore the geo-biological and cultural heritage of different regions of Africa over various periods, from deep time to the Anthropocene. Each corridor reveals a specific lens through which to investigate some of the rich scientific narratives embedded within it. The concept also facilitates learning and knowledge exchange across numerous disciplines: archeology, geology, geophysics, oceanography, glaciology, biology, botany, ecology, agriculture, engineering, spatial statistics, social sciences, and the humanities. This contribution analyses ten selected corridors in southern and western Africa, the Congo Basin, East Africa, and Madagascar. The various research themes explored include Earth impact hazard, origins of humankind, Snowball Earth, coastal food systems and conservation, the biogeography of lemurs, human settlement dynamics in Cameroon, tectonically linked earthquake occurrences in Algeria and Morocco, modelling land-use changes in the Western Rift Valley, trades and civilizations of the Mali Empire, Mbira music, and contemporary art. The ongoing work on these—and ten other—corridors has considerable potential to host new international collaborations to develop the links between society and natural sciences in Africa. Ultimately, AAC will benefit all stakeholders, especially the youth, in understanding and responding to societal needs and current global challenges.

The reorganization of predator–prey networks over 20 million years explains extinction patterns of mammalian carnivores - João C. S. Nascimento; Fernando Blanco; M. Soledad Domingo; Juan L. Cantalapiedra; Mathias M. Pires (Ecology Letters, 2024)
Linking the species interactions occurring at the scale of local communities to their potential impact at evolutionary timescales is challenging. Here, we used the high‐resolution fossil record of mammals from the Iberian Peninsula to reconstruct a timeseries of trophic networks spanning more than 20 million years and asked whether predator–prey interactions affected regional extinction patterns. We found that, despite small changes in species richness, trophic networks showed long‐term trends, gradually losing interactions and becoming sparser towards the present. This restructuring of the ecological networks was driven by the loss of medium‐sized herbivores, which reduced prey availability for predators. The decrease in prey availability was associated with predator longevity, such that predators with less available prey had greater extinction risk. These results not only reveal long‐term trends in network structure but suggest that prey species richness in ecological communities may shape large scale patterns of extinction and persistence among predators.

Enhancing agency and empowerment in agricultural development projects: A synthesis of mixed methods impact evaluations from the Gender, Agriculture, and Assets Project, Phase 2 (GAAP2) - Agnes R. Quisumbing; Ruth Meinzen-Dick; Hazel J. Malapit; Greg Seymour; Jessica Heckert; Cheryl Doss; Nancy Johnson; Deborah Rubin; Giang Thai; Gayathri Ramani; Emily Myers; Agnes Quisumbing; et al. (Journal of Rural Studies, 2024)

Long-term soil organic carbon and crop yield feedbacks differ between 16 soil-crop models in sub-Saharan Africa - Antoine Couëdel; Gatien N. Falconnier; Myriam Adam; Rémi Cardinael; Kenneth Boote; Eric Justes; Ward N. Smith; Anthony M. Whitbread; François Affholder; Juraj Balkovic; Bruno Basso; Arti Bhatia; et al. (European Journal of Agronomy, 2024)

Brownification in the Eastern Mediterranean Sea: effect of simulated terrestrial input on the planktonic microbial food web in an oligotrophic sea - Georgia Ktistaki; Iordanis Magiopoulos; Gianluca Corno; Justine Courboulès; Ester M. Eckert; Jose González; Ioanna Kalantzi; Mathias Middelboe; Katerina Symiakaki; Manolis Tsapakis; Francesca Vidussi; Paraskevi Pitta (Frontiers in Marine Science, 2024)
Terrestrial input to marine and freshwater ecosystems colors the water yellow-brown, causing a phenomenon called “brownification”. The effect of brownification on the marine pelagic microbial food web was studied in the oligotrophic eastern Mediterranean in June 2021 by adding HuminFeed in a 15-day mesocosm experiment with 2 treatments: Control (C, no addition) and HuminFeed (HF, single dose of HuminFeed, 2 mg L -1 ); and 3 replicates per treatment. HuminFeed caused shading, leading to a decrease in the abundance of photo-autotrophic organisms (cyanobacteria Synechococcus and diatoms). Bacteria were positively affected by the HF addition (mainly in terms of production rather than abundance), benefiting either directly from the dissolved organic carbon (DOC) contained in HuminFeed or indirectly from the trophic cascade through the food web. Despite the decrease in HF bacterial abundance during the experiment, an increase in both the high nucleic acid containing bacteria% and heterotrophic bacterial production were observed, suggesting higher activity at the single cell level. In the HF treatment, the increased abundance of dinoflagellates observed could be due to either a dominance of mixotrophic species or a release from predation by copepods. Both ciliates and copepods were severely impacted by HuminFeed, showing lower abundance and distorted forms (ciliates) and reduced reproductive potential (copepods). In conclusion, in the ultraoligotrophic eastern Mediterranean, the simulated brownification negatively affected autotrophs and top predators while benefiting bacteria, thus indicating a shift in the structure of the plankton food web.

Understanding different dominance patterns in western Amazonian forests - Laura Matas‐Granados; Frederick C. Draper; Luis Cayuela; Julia G. de Aledo; Gabriel Arellano; Celina Ben Saadi; Timothy R. Baker; Oliver L. Phillips; Eurídice N. Honorio Coronado; Kalle Ruokolainen; Roosevelt García‐Villacorta; Katherine H. Roucoux; et al. (Ecology Letters, 2024)
Dominance of neotropical tree communities by a few species is widely documented, but dominant trees show a variety of distributional patterns still poorly understood. Here, we used 503 forest inventory plots (93,719 individuals ≥2.5 cm diameter, 2609 species) to explore the relationships between local abundance, regional frequency and spatial aggregation of dominant species in four main habitat types in western Amazonia. Although the abundance‐occupancy relationship is positive for the full dataset, we found that among dominant Amazonian tree species, there is a strong negative relationship between local abundance and regional frequency and/or spatial aggregation across habitat types. Our findings suggest an ecological trade‐off whereby dominant species can be locally abundant ( local dominants ) or regionally widespread ( widespread dominants ), but rarely both ( oligarchs ). Given the importance of dominant species as drivers of diversity and ecosystem functioning, unravelling different dominance patterns is a research priority to direct conservation efforts in Amazonian forests.

Practical Guide to Measuring Wetland Carbon Pools and Fluxes - Sheel Bansal; Irena F. Creed; Brian A. Tangen; Scott D. Bridgham; Ankur R. Desai; Ken W. Krauss; Scott C. Neubauer; Gregory B. Noe; Donald O. Rosenberry; Carl Trettin; Kimberly P. Wickland; Scott T. Allen; et al. (Wetlands, 2023)
Wetlands cover a small portion of the world, but have disproportionate influence on global carbon (C) sequestration, carbon dioxide and methane emissions, and aquatic C fluxes. However, the underlying biogeochemical processes that affect wetland C pools and fluxes are complex and dynamic, making measurements of wetland C challenging. Over decades of research, many observational, experimental, and analytical approaches have been developed to understand and quantify pools and fluxes of wetland C. Sampling approaches range in their representation of wetland C from short to long timeframes and local to landscape spatial scales. This review summarizes common and cutting-edge methodological approaches for quantifying wetland C pools and fluxes. We first define each of the major C pools and fluxes and provide rationale for their importance to wetland C dynamics. For each approach, we clarify what component of wetland C is measured and its spatial and temporal representativeness and constraints. We describe practical considerations for each approach, such as where and when an approach is typically used, who can conduct the measurements (expertise, training requirements), and how approaches are conducted, including considerations on equipment complexity and costs. Finally, we review key covariates and ancillary measurements that enhance the interpretation of findings and facilitate model development. The protocols that we describe to measure soil, water, vegetation, and gases are also relevant for related disciplines such as ecology. Improved quality and consistency of data collection and reporting across studies will help reduce global uncertainties and develop management strategies to use wetlands as nature-based climate solutions.

Climate change should drive mammal defaunation in tropical dry forests - Mario R. Moura; Gibran A. Oliveira; Adriano P. Paglia; Mathias M. Pires; Bráulio A. Santos (Global Change Biology, 2023)
Human‐induced climate change has intensified negative impacts on socioeconomic factors, the environment, and biodiversity, including changes in rainfall patterns and an increase in global average temperatures. Drylands are particularly at risk, with projections suggesting they will become hotter, drier, and less suitable for a significant portion of their species, potentially leading to mammal defaunation. We use ecological niche modelling and community ecology biodiversity metrics to examine potential geographical range shifts of non‐volant mammal species in the largest Neotropical dryland, the Caatinga, and evaluate impacts of climate change on mammal assemblages. According to projections, 85% of the mammal species will lose suitable habitats, with one quarter of species projected to completely lose suitable habitats by 2060. This will result in a decrease in species richness for more than 90% of assemblages and an increase in compositional similarity to nearby assemblages (i.e., reduction in spatial beta diversity) for 70% of the assemblages. Small‐sized mammals will be the most impacted and lose most of their suitable habitats, especially in highlands. The scenario is even worse in the eastern half of Caatinga where habitat destruction already prevails, compounding the threats faced by species there. While species‐specific responses can vary with respect to dispersal, behavior, and energy requirements, our findings indicate that climate change can drive mammal assemblages to biotic homogenization and species loss, with drastic changes in assemblage trophic structure. For successful long‐term socioenvironmental policy and conservation planning, it is critical that findings from biodiversity forecasts are considered.

Oligocene to Pleistocene mudwhelks (Gastropoda: Potamididae, Batillariidae) of the Eurasian Paratethys Sea – Diversity, origins and mangroves - Mathias Harzhauser; Aleksandr Guzhov; Bernard M. Landau; Andrea K. Kern; Thomas A. Neubauer (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Combined effects of temperature and emersion-immersion cycles on metabolism and bioenergetics of the Pacific oyster Crassostrea (Magallana) gigas - Torben Bruhns; Stefan Timm; Nina Feußner; Sonja Engelhaupt; Matthias Labrenz; Mathias Wegner; Inna M. Sokolova (Marine Environmental Research, 2023)

Closing the gap between science and management of cold‐water refuges in rivers and streams - Francine H. Mejia; Valerie Ouellet; Martin A. Briggs; Stephanie M. Carlson; Roser Casas‐Mulet; Mollie Chapman; Mathias J. Collins; Stephen J. Dugdale; Joseph L. Ebersole; Danielle M. Frechette; Aimee H. Fullerton; Carole‐Anne Gillis; et al. (Global Change Biology, 2023)
Human activities and climate change threaten coldwater organisms in freshwater ecosystems by causing rivers and streams to warm, increasing the intensity and frequency of warm temperature events, and reducing thermal heterogeneity. Cold‐water refuges are discrete patches of relatively cool water that are used by coldwater organisms for thermal relief and short‐term survival. Globally, cohesive management approaches are needed that consider interlinked physical, biological, and social factors of cold‐water refuges. We review current understanding of cold‐water refuges, identify gaps between science and management, and evaluate policies aimed at protecting thermally sensitive species. Existing policies include designating cold‐water habitats, restricting fishing during warm periods, and implementing threshold temperature standards or guidelines. However, these policies are rare and uncoordinated across spatial scales and often do not consider input from Indigenous peoples. We propose that cold‐water refuges be managed as distinct operational landscape units, which provide a social and ecological context that is relevant at the watershed scale. These operational landscape units provide the foundation for an integrated framework that links science and management by (1) mapping and characterizing cold‐water refuges to prioritize management and conservation actions, (2) leveraging existing and new policies, (3) improving coordination across jurisdictions, and (4) implementing adaptive management practices across scales. Our findings show that while there are many opportunities for scientific advancement, the current state of the sciences is sufficient to inform policy and management. Our proposed framework provides a path forward for managing and protecting cold‐water refuges using existing and new policies to protect coldwater organisms in the face of global change.

Interaction time with conspecifics induces food preference or aversion in the wild Algerian mouse - Rita S. Andrade; Ana M. Cerveira; Maria da Luz Mathias; Susana A.M. Varela (Behavioural Processes, 2023)

Effect of reverse osmosis pre-processing of acid whey and electrodialysis current density on process performance - Emilie N. Nielsen; Mathias Gøtke; Ulysse Cordin; Leif H. Skibsted; Svetlozar Velizarov; João G. Crespo; Lilia M. Ahrné (Food and Bioproducts Processing, 2023)

Where are we now with European forest multi-taxon biodiversity and where can we head to? - Sabina Burrascano; Francesco Chianucci; Giovanni Trentanovi; Sebastian Kepfer-Rojas; Tommaso Sitzia; Flóra Tinya; Inken Doerfler; Yoan Paillet; Thomas Andrew Nagel; Bozena Mitic; Lourdes Morillas; Silvana Munzi; et al. (Biological Conservation, 2023)

Identifying climate change refugia for South American biodiversity - Lilian P. Sales; Mathias M. Pires (Conservation Biology, 2023)
Refugia‐based conservation offers long‐term effectiveness and minimize uncertainty on strategies for climate change adaptation. We used distribution modelling to identify climate change refugia for 617 terrestrial mammals and to quantify the role of protected areas (PAs) in providing refugia across South America. To do so, we compared species potential distribution across different scenarios of climate change, highlighting those regions likely to retain suitable climatic conditions by year 2090, and explored the proportion of refugia inside PAs. Moist tropical forests in high‐elevation areas with complex topography concentrated the highest local diversity of species refugia, although regionally important refugia centers occurred elsewhere. Andean–Amazon forests contained climate change refugia for more than half of the continental species’ pool and for up to 87 species locally (17 × 17 km 2 grid cell). The highlands of the southern Atlantic Forest also included megadiverse refugia for up to 76 species per cell. Almost half of the species that may find refugia in the Atlantic Forest will do so in a single region—the Serra do Mar and Serra do Espinhaço. Most of the refugia we identified, however, were not in PAs, which may contain

Captivity induces a sweeping and sustained genomic response in a starfish - Marie Morin; Mathias Jönsson; Conan K. Wang; David J. Craik; Sandie M. Degnan; Bernard M. Degnan (Molecular Ecology, 2023)
Marine animals in the wild are often difficult to access, so they are studied in captivity. However, the implicit assumption that physiological processes of animals in artificial environments are not different from those in the wild has rarely been tested. Here, we investigate the extent to which an animal is impacted by captivity by comparing global gene expression in wild and captive crown‐of‐thorns starfish (COTS). In a preliminary analysis, we compared transcriptomes of three external tissues obtained from multiple wild COTS with a single captive COTS maintained in aquaria for at least 1 week. On average, an astonishingly large 24% of the coding sequences in the genome were differentially expressed. This led us to conduct a replicated experiment to test more comprehensively the impact of captivity on gene expression. Specifically, a comparison of 13 wild with 8 captive COTS coelomocyte transcriptomes revealed significant differences in the expression of 20% of coding sequences. Coelomocyte transcriptomes in captive COTS remain different from those in wild COTS for more than 30 days and show no indication of reverting back to a wild state (i.e. no evidence of acclimation). Genes upregulated in captivity include those involved in oxidative stress and energy metabolism, whereas genes downregulated are involved in cell signalling. These changes in gene expression indicate that being translocated and maintained in captivity has a marked impact on the physiology and health of these echinoderms. This study suggests that caution should be exercised when extrapolating results from captive aquatic invertebrates to their wild counterparts.

Depolymerization of enzymatic hydrolysis lignin: Review of technologies and opportunities for research - Fabricia F. Menezes; Viviane M. Nascimento; Gustavo R. Gomes; George. J.M. Rocha; Mathias Strauss; Tassia L. Junqueira; Carlos Driemeier (Fuel, 2023)

Implementation During a Pandemic: Findings, Successes, and Lessons Learned from Community Grantees - Wilhelmenia Mathias; Karen A. Nichols; Jewel Golden-Wright; Ciaran M. Fairman; Tisha M. Felder; Lauren Workman; Karen E. Wickersham; Kimberly J. Flicker; Jingxi Sheng; Samuel B. Noblet; Swann Arp Adams; Jan M. Eberth; et al. (Journal of Cancer Education, 2023)

Differences in leaf gas exchange strategies explain Quercus rubra and Liriodendron tulipifera intrinsic water use efficiency responses to air pollution and climate change - Justin M. Mathias; Kenneth R. Smith; Kristin E. Lantz; Keanan T. Allen; Marvin J. Wright; Afsoon Sabet; Kristina J. Anderson‐Teixeira; Richard B. Thomas (Global Change Biology, 2023)
Trees continuously regulate leaf physiology to acquire CO 2 while simultaneously avoiding excessive water loss. The balance between these two processes, or water use efficiency (WUE), is fundamentally important to understanding changes in carbon uptake and transpiration from the leaf to the globe under environmental change. While increasing atmospheric CO 2 (iCO 2 ) is known to increase tree intrinsic water use efficiency (iWUE), less clear are the additional impacts of climate and acidic air pollution and how they vary by tree species. Here, we couple annually resolved long‐term records of tree‐ring carbon isotope signatures with leaf physiological measurements of Quercus rubra ( Quru ) and Liriodendron tulipifera ( Litu ) at four study locations spanning nearly 100 km in the eastern United States to reconstruct historical iWUE, net photosynthesis ( A net ), and stomatal conductance to water ( g s ) since 1940. We first show 16%–25% increases in tree iWUE since the mid‐20th century, primarily driven by iCO 2 , but also document the individual and interactive effects of nitrogen (NO x ) and sulfur (SO 2 ) air pollution overwhelming climate. We find evidence for Quru leaf gas exchange being less tightly regulated than Litu through an analysis of isotope‐derived leaf internal CO 2 (C i ), particularly in wetter, recent years. Modeled estimates of seasonally integrated A net and g s revealed a 43%–50% stimulation of A net was responsible for increasing iWUE in both tree species throughout 79%–86% of the chronologies with reductions in g s attributable to the remaining 14%–21%, building upon a growing body of literature documenting stimulated A net overwhelming reductions in g s as a primary mechanism of increasing iWUE of trees. Finally, our results underscore the importance of considering air pollution, which remains a major environmental issue in many areas of the world, alongside climate in the interpretation of leaf physiology derived from tree rings.

Decoupled responses of biodiversity facets driven from anuran vulnerability to climate and land‐use changes - Karoline Ceron; Lilian P. Sales; Diego J. Santana; Mathias M. Pires (Ecology Letters, 2023)
Biodiversity loss not only implies the loss of species but also entails losses in other dimensions of biodiversity, such as functional, phylogenetic and interaction diversity. Yet, each of those facets of biodiversity may respond differently to extinctions. Here, we examine how extinction, driven by climate and land‐use changes may affect those different facets of diversity by combining empirical data on anuran–prey interaction networks, species distribution modelling and extinction simulations in assemblages representing four Neotropical ecoregions. We found a mismatch in the response of functional, phylogenetic and interaction diversity to extinction. In spite of high network robustness to extinction, the effects on interaction diversity were stronger than those on phylogenetic and functional diversity, declining linearly with species loss. Although it is often assumed that interaction patterns are reflected by functional diversity, assessing species interactions may be necessary to understand how species loss translates into the loss of ecosystem functions.

Atlantic ITCZ variability during the Holocene based on high-resolution speleothem isotope records from northern Venezuela - N. Melissa M. Medina; Francisco W. Cruz; Amos Winter; Haiwei Zhang; Angela Ampuero; Mathias Vuille; Víctor C. Mayta; Marília C. Campos; Verónica Marcela Rámirez; Giselle Utida; Andrés Camilo Zúñiga; Hai Cheng (Quaternary Science Reviews, 2023)

European Dendroecological Fieldweek (EDF) 2021 in Val Müstair, Switzerland: International education and research during the pandemic - Kerstin Treydte; Elisabet Martínez-Sancho; Isabel Dorado-Liñán; Ryszard J. Kaczka; Linda Feichtinger; Anne Verstege; Kelley R. Bassett; Patrick Cassitti; Roberta D'Andrea; Olympia Facchinetti; Costanza M. Fileccia; Nazimul Islam; et al. (Dendrochronologia, 2023)

A linear SARS-CoV-2 DNA vaccine candidate reduces virus shedding in ferrets - Mathias Martins; Gabriela M. do Nascimento; Antonella Conforti; Jessica C. G. Noll; Joseph A. Impellizeri; Elisa Sanchez; Bettina Wagner; Lucia Lione; Erika Salvatori; Eleonora Pinto; Mirco Compagnone; Brian Viscount; et al. (Archives of Virology, 2023)

Impact of land cover, rainfall and topography on flood risk in West Java - Rahmawati Rahayu; Simon A. Mathias; Sim Reaney; Gianni Vesuviano; Rusmawan Suwarman; Agus M. Ramdhan (Natural Hazards, 2023)
Flooding represents around 32% of total disasters in Indonesia and disproportionately affects the poorest of communities. The objective of this study was to determine significant statistical differences, in terms of river catchment characteristics, between regions in West Java that reported suffering from flood disasters and those that did not. Catchment characteristics considered included various statistical measures of topography, land-use, soil-type, meteorology and river flow rates. West Java comprises 154 level 9 HydroSHEDS sub-basin regions. We split these regions into those where flood disasters were reported and those where they were not, for the period of 2009 to 2013. Rainfall statistics were derived using the CHIRPS gridded precipitation data package. Statistical estimates of river flow rates, applicable to ungauged catchments, were derived from regionalisation relationships obtained by stepwise linear regression with river flow data from 70 West Javanese gauging stations. We used Kolmogorov–Smirnov tests to identify catchment characteristics that exhibit significant statistical differences between the two sets of regions. Median annual maximum river flow rate (AMRFR) was found to be positively correlated with plantation cover. Reducing plantation land cover from 20 to 10% was found to lead to a modelled 38% reduction in median AMRFR. AMRFR with return periods greater than 10 years were found to be negatively correlated with wetland farming land cover, suggesting that rice paddies play an important role in attenuating extreme river flow events. Nevertheless, the Kolmogorov–Smirnov tests revealed that built land cover is the most important factor defining whether or not an area is likely to report flood disasters in West Java. This is presumably because the more built land cover, the more people available to experience and report flood disasters. Our findings also suggest that more research is needed to understand the important role of plantation cover in aggravating median annual maximum river flow rates and wetland farming cover in mitigating extreme river flow events.

Pan‐Arctic soil moisture control on tundra carbon sequestration and plant productivity - Donatella Zona; Peter M. Lafleur; Koen Hufkens; Beniamino Gioli; Barbara Bailey; George Burba; Eugénie S. Euskirchen; Jennifer D. Watts; Kyle A. Arndt; Mary Farina; John S. Kimball; Martin Heimann; et al. (Global Change Biology, 2023)
Long‐term atmospheric CO 2 concentration records have suggested a reduction in the positive effect of warming on high‐latitude carbon uptake since the 1990s. A variety of mechanisms have been proposed to explain the reduced net carbon sink of northern ecosystems with increased air temperature, including water stress on vegetation and increased respiration over recent decades. However, the lack of consistent long‐term carbon flux and in situ soil moisture data has severely limited our ability to identify the mechanisms responsible for the recent reduced carbon sink strength. In this study, we used a record of nearly 100 site‐years of eddy covariance data from 11 continuous permafrost tundra sites distributed across the circumpolar Arctic to test the temperature (expressed as growing degree days, GDD) responses of gross primary production (GPP), net ecosystem exchange (NEE), and ecosystem respiration (ER) at different periods of the summer (early, peak, and late summer) including dominant tundra vegetation classes (graminoids and mosses, and shrubs). We further tested GPP, NEE, and ER relationships with soil moisture and vapor pressure deficit to identify potential moisture limitations on plant productivity and net carbon exchange. Our results show a decrease in GPP with rising GDD during the peak summer (July) for both vegetation classes, and a significant relationship between the peak summer GPP and soil moisture after statistically controlling for GDD in a partial correlation analysis. These results suggest that tundra ecosystems might not benefit from increased temperature as much as suggested by several terrestrial biosphere models, if decreased soil moisture limits the peak summer plant productivity, reducing the ability of these ecosystems to sequester carbon during the summer.

Caudal fin as a proxy for dorsal muscle for nutrient enrichment monitoring using stable isotope analysis: the case of Gerres filamentosus and G. oyena from mangrove creeks of Tanzania - Blandina R. Lugendo; Mathias M. Igulu; Masumbuko L. Semba; Ismael A. Kimirei (Western Indian Ocean Journal of Marine Science, 2023)
The use of fish dorsal muscles in stable isotope studies, which is an invasive method that results in fish deaths, limits their applicability for rare and endangered fish species, as well as when large sample sizes and replicates are required, prompting research into feasible non-lethal sampling methods. The possibility of employing fin clippings (a non invasive approach) was investigated as a proxy for dorsal muscle in nutrient pollution monitoring studies using two common mangrove fish species, namely Gerres filamentosus and G. oyena, which are known to spend their early life stages primarily within mangroves. The dorsal muscles and caudal fin tissues of fish from the mangrove creeks of Kunduchi and Mbegani, Tanzania, were examined for 13C and 15N signatures. Dorsal muscles from Kunduchi (mean SD: 13C = -16.8 ± 2.86, 15N = 9.34±1.15) were more enriched than from Mbegani (mean SD: 13C = -18.60 ± 2.11, 15N = 7.27±1.09), and this enrichment was consistent across the two studied species. Caudal fins indicated similar enrichment trends. Fin tissue stable isotope values explained between 62 % and 87 % of dorsal muscle 13C and between 89 % and 98 % of dorsal muscle 15N variability. These findings support the use of fin-clipping as a non-lethal proxy for stable isotope analysis of the studied species for nutrient enrichment, and additional research into non-lethal sampling methods is recommended.

Energy-effective and low-cost carbon capture from point-sources enabled by water-lean solvents - Yuan Jiang; Paul M. Mathias; Richard F. Zheng; Charlies J. Freeman; Dushyant Barpaga; Deepika Malhotra; Phillip K. Koech; Andy Zwoster; David J. Heldebrant (Journal of Cleaner Production, 2023)

Introduced species in a tidal ecosystem of mud and sand: curse or blessing? - Karsten Reise; Christian Buschbaum; Dagmar Lackschewitz; David W. Thieltges; Andreas M. Waser; K. Mathias Wegner (Marine Biodiversity, 2023)
For about a century, biodiversity in the tidal Wadden Sea (North Sea, European Atlantic) has increased by more than one hundred introduced species from overseas. Most originate from warmer waters and could facilitate the transformation of this coastal ecosystem to comply with climate warming. Some introduced species promote sediment stabilization and mud accretion. This could help tidal flats to keep up with sea level rise. Although some introduced species also entail negative effects, introductions have diversified lower food web levels, and may benefit foraging birds. So far, no resident populations have gone extinct because an introduced species had established. Rather than degrading the ecosystem, the establishment of introduced species seems to have raised the capacity to follow environmental change. We support increasing efforts against introductions to avoid risk. However, once species are integrated, the common condemnation attitude against “non-natives” or “aliens” ought to be reconsidered for tidal ecosystems of low biodiversity.

Correction to: The Impact of Three-Dimensional Effects on the Simulation of Turbulence Kinetic Energy in a Major Alpine Valley - Brigitta Goger; Mathias W. Rotach; Alexander Gohm; Oliver Fuhrer; Ivana Stiperski; Albert A. M. Holtslag (Boundary-Layer Meteorology, 2023)
The funding agency information in the Acknowledgements was not complete in the original publication of the article. The revised Acknowledgments is provided in this erratum.

isocalcR : An R package to streamline and standardize stable isotope calculations in ecological research - Justin M. Mathias; Tara W. Hudiburg (Global Change Biology, 2022)
The use of stable isotopes to characterize ecosystem dynamics and infer leaf gas exchange processes has become increasingly prevalent over the last few decades within the ecological community. While advancements in theory and our understanding of the physiological processes controlling isotopic signatures in plants has been well‐documented, no standardized tool currently exists to facilitate the computation of common isotope‐derived plant physiological indices. Here, we present isocalcR , an R package intended to facilitate the use of stable isotope data from plant tissues by providing an integrated collection of functions and recommended reference data. The isocalcR R package contains a suite of functions that compute leaf carbon isotope discrimination (∆ 13 C), leaf intercellular [CO 2 ], the ratio of leaf intercellular to atmospheric [CO 2 ], the difference between atmospheric and leaf intercellular [CO 2 ], and intrinsic water use efficiency from carbon isotope signatures in leaf or wood tissue with minimal inputs from the user. isocalcR also implements and provides recommended input atmospheric [CO 2 ] (ppm) and atmospheric δ 13 CO 2 (‰) data for the period 0–2021 C.E. A major goal of isocalcR is to provide a standardized, open‐source tool to streamline the calculation of reproducible physiological indices from stable isotope signatures in plant tissues, incorporating the most up‐to‐date theory, while simultaneously eliminating potential errors associated with complex calculations. isocalcR can be used for any location globally as long as the user provides information regarding temperature and elevation to the main workhorse functions.

Relating QRS voltages to left ventricular mass and body composition in elite endurance athletes - Ruben De Bosscher; Jonathan Moeyersons; Christophe Dausin; Mathias Claeys; Kristel Janssens; Piet Claus; Kaatje Goetschalckx; Jan Bogaert; Caroline M. Van De Heyning; Bernard Paelinck; Prashanthan Sanders; Jonathan Kalman; et al. (European Journal of Applied Physiology, 2022)

Lowering water table reduces carbon sink strength and carbon stocks in northern peatlands - Min Jung Kwon; Ashley Ballantyne; Philippe Ciais; Chunjing Qiu; Elodie Salmon; Nina Raoult; Bertrand Guenet; Mathias Göckede; Eugénie S. Euskirchen; Hannu Nykänen; Edward A. G. Schuur; Merritt R. Turetsky; et al. (Global Change Biology, 2022)
Peatlands at high latitudes have accumulated >400 Pg carbon (C) because saturated soil and cold temperatures suppress C decomposition. This substantial amount of C in Arctic and Boreal peatlands is potentially subject to increased decomposition if the water table (WT) decreases due to climate change, including permafrost thaw‐related drying. Here, we optimize a version of the Organizing Carbon and Hydrology In Dynamic Ecosystems model (ORCHIDEE‐PCH4) using site‐specific observations to investigate changes in CO 2 and CH 4 fluxes as well as C stock responses to an experimentally manipulated decrease of WT at six northern peatlands. The unmanipulated control peatlands, with the WT −2 year −1 ; including 6 ± 7 g C–CH 4 m −2 year −1 emission). We found, however, that lowering the WT by 10 cm reduced the CO 2 sink by 13 ± 15 g C m −2 year −1 and decreased CH 4 emission by 4 ± 4 g CH 4 m −2 year −1 , thus accumulating less C over 100 years (0.2 ± 0.2 kg C m −2 ). Yet, the reduced emission of CH 4 , which has a larger greenhouse warming potential, resulted in a net decrease in greenhouse gas balance by 310 ± 360 g CO 2‐eq m −2 year −1 . Peatlands with the initial WT close to the soil surface were more vulnerable to C loss: Non‐permafrost peatlands lost >2 kg C m −2 over 100 years when WT is lowered by 50 cm, while permafrost peatlands temporally switched from C sinks to sources. These results highlight that reductions in C storage capacity in response to drying of northern peatlands are offset in part by reduced CH 4 emissions, thus slightly reducing the positive carbon climate feedbacks of peatlands under a warmer and drier future climate scenario.

Genome sequence and experimental infection of calves with bovine gammaherpesvirus 4 (BoHV-4) - Fernando V. Bauermann; Shollie M. Falkenberg; Mathias Martins; Rohana P. Dassanayake; John D. Neill; Julia F. Ridpath; Simone Silveira; Mitchel V. Palmer; Alaine Buysse; Anna Mohr; Eduardo F. Flores; Diego G. Diel (Archives of Virology, 2022)

Differences in prey availability across space and time lead to interaction rewiring and reshape a predator–prey metaweb - Karoline Ceron; Diogo B. Provete; Mathias M. Pires; Andréa C. Araujo; Nico Blüthgen; Diego J. Santana (Ecology, 2022)
Space and time promote variation in network structure by affecting the likelihood of potential interactions. However, little is known about the relative roles of ecological and biogeographical processes in determining how species interactions vary across space and time. Here we study the spatiotemporal variation in predator–prey interaction networks formed by anurans and arthropods and test for the effects of prey availability in determining interaction patterns, information that is often absent and limits the understanding of the determinants of network structure. We found that network dissimilarity between ecoregions and seasons was high and primarily driven by interaction rewiring.We also found that species turnover was positively related to geographical distance. Using a null model approach to disentangle the effect of prey availability on the spatial and temporal variation, we show that differences in prey availability were important in determining the variation in network structure between seasons and among areas. Our study reveals that fluctuations in prey abundance, alongside the limited dispersal abilities of anurans and their prey, may be responsible for the spatial patterns that emerged in our predator–prey metaweb. These findings contribute to our understanding of the assembly rules that maintain biotic processes in metacommunities and highlight the importance of prey availability to the structure of these systems.

Body mass ratios determine dietary patterns and help predicting predator–prey interactions of Neotropical Carnivora - Lívia R. Cruz; Mathias M. Pires (Mammal Research, 2022)

Interlaboratory comparison of an intestinal triple culture to confirm transferability and reproducibility - Angela A. M. Kämpfer; Ume-Kulsoom Shah; Shui L. Chu; Mathias Busch; Veronika Büttner; Ruiwen He; Barbara Rothen-Rutishauser; Roel P. F. Schins; Gareth J. Jenkins (In vitro models, 2022)
The development and improvement of advanced intestinal in vitro models has received increasing attention in recent years. While the availability of relevant in vitro models is pivotal to advance the replacement and reduction of animal use in research, their robustness is a crucial determinant for intra- and interlaboratory reproducibility. We have developed a standard protocol to build a triple culture model combining two types of human intestinal epithelial cells (Caco-2, HT29-MTX-E12) and macrophages (THP-1), which was tested for transferability and reproducibility between three laboratories. The epithelial tissue barrier development and triple culture stability were investigated as well as the models’ responses to the non-steroidal anti-inflammatory drug diclofenac in terms of barrier integrity, cytotoxicity, and cytokine release. The results of two partner laboratories were compared to previously established benchmark results and quality criteria. For the epithelial co-cultures, the results were overall highly comparable between the laboratories. The addition of THP-1 cells resulted in increased variability and reduced reproducibility. While good correlation was achieved in several endpoints, others showed substantial response differences between the laboratories. Some variations may be addressed with training or demonstrations, whereas others might be related to fundamental differences in the cell lines introduced during routine cell culture and maintenance. Our results underline the importance of interlaboratory transfer studies using standardised experimental procedures, including defined quality criteria and benchmarks, as well as of training when newly establishing complex in vitro models in laboratories.

The effect of past defaunation on ranges, niches, and future biodiversity forecasts - Lilian P. Sales; Mauro Galetti; Ana Carnaval; Sophie Monsarrat; Jens‐Christian Svenning; Mathias M. Pires (Global Change Biology, 2022)
Humans have reshaped the distribution of biodiversity across the globe, extirpating species from regions otherwise suitable and restricting populations to a subset of their original ranges. Here, we ask if anthropogenic range contractions since the Late Pleistocene led to an under‐representation of the realized niches for megafauna, an emblematic group of taxa often targeted for restoration actions. Using reconstructions of past geographic distributions (i.e., natural ranges ) for 146 extant terrestrial large‐bodied (>44 kg) mammals, we estimate their climatic niches as if they had retained their original distributions and evaluate their observed niche dynamics. We found that range contractions led to a sizeable under‐representation of the realized niches of several species (i.e., niche unfilling ). For 29 species, more than 10% of the environmental space once seen in their natural ranges has been lost due to anthropogenic activity, with at least 12 species undergoing reductions of more than 50% of their realized niches. Eighteen species may now be confined to low‐suitability locations, where fitness and abundance are likely diminished; we consider these taxa ' climatic refugees' . For those species, conservation strategies supported by current ranges risk being misguided if current, suboptimal habitats are considered baseline for future restoration actions. Because most climate‐based biodiversity forecasts rely exclusively on current occurrence records, we went on to test the effect of neglecting historical information on estimates of species’ potential distribution – as a proxy of sensitivity to climate change. We found that niche unfilling driven by past range contraction leads to an overestimation of sensitivity to future climatic change, resulting in 50% higher rates of global extinction, and underestimating the potential for megafauna conservation and restoration under future climate change. In conclusion, range contractions since the Late Pleistocene have also left imprints on megafauna realized climatic niches. Therefore, niche truncation driven by defaunation can directly affect climate and habitat‐based conservation strategies.

Madagascar Terrestrial Camera Survey Database 2021: A collation of protected forest camera surveys from 2007–2021 - Erin M. Wampole; Brian D. Gerber; Zach J. Farris; Jean Claude Razafimahaimodison; Mahandry Hugues Andrianarisoa; Claude Jacquot Ralazampirenena; Patricia C. Wright; C. Delaid Rasamisoa; Dean Gibson; Mathias W. Tobler; Timothy M. Eppley; Natalie Vasey; et al. (Ecology, 2022)
Madagascar is a threatened global biodiversity hotspot and conservation priority, yet we lack broad‐scale surveys to assess biodiversity across space and time. To fill this gap, we collated camera trap surveys, capturing species occurrences within Madagascar into a single standardized database. This data set includes nine distinct protected areas of Madagascar and encompasses 13 subprojects, 38 camera arrays, and 1156 sampling units (independent camera site per survey) within two important biodiversity eco‐regions: western dry deciduous forest and eastern humid rainforest. Camera surveys were conducted from June 2007 to January 2021. The final data set includes 17 unique families of mammals (Bovidae, Canidae, Cheirogaleidae, Daubentoniidae, Equidae, Eupleridae, Felidae, Hominidae, Indriidae, Lemuridae, Lepilemuridae, Muridae, Nesomyidae, Pteropodidae, Soricidae, Suidae, Tenrecidae) comprising 45 species and 27 unique families of birds (Accipitridae, Acrocephalidae, Alcedinidae, Bernieridae, Brachypteraciidae, Caprimulgidae, Cisticolidae, Columbidae, Coraciidae, Corvidae, Cuculidae, Dicruridae, Mesitornithidae, Monarchidae, Motacillidae, Muscicapidae, Numididae, Phasianidae, Rallidae, Sarothruridae, Strigidae, Sturnidae, Sulidae, Threskiornithidae, Upupidae, Vangidae, Zosteropidae) comprising 58 species. Images were processed and verified by individual project data set creators and camera operation and species tables were then collated. The final product represents the first broad‐scale freely available standardized formal faunal database for Madagascar. Data are available through this publication and at DOI: 10.5281/zenodo.5801806. These data will be useful for examining species‐level and community‐level trends in occurrence across space or time within Madagascar and globally, evaluating native and invasive species dynamics, and will aid in determining species conservation status and planning for at‐risk species. There are no copyright restrictions; please cite this paper when using the data for publication.

MAMMALS IN PORTUGAL : A data set of terrestrial, volant, and marine mammal occurrences in P ortugal - Clara Grilo; Beatriz C. Afonso; Filipe Afonso; Marta Alexandre; Sara Aliácar; Ana Almeida; Ivan Prego Alonso; Francisco Álvares; Paulo Alves; Paulo Célio Alves; Pedro Alves; Anabela Amado; et al. (Ecology, 2022)
Mammals are threatened worldwide, with ~26% of all species being included in the IUCN threatened categories. This overall pattern is primarily associated with habitat loss or degradation, and human persecution for terrestrial mammals, and pollution, open net fishing, climate change, and prey depletion for marine mammals. Mammals play a key role in maintaining ecosystems functionality and resilience, and therefore information on their distribution is crucial to delineate and support conservation actions. MAMMALS IN PORTUGAL is a publicly available data set compiling unpublished georeferenced occurrence records of 92 terrestrial, volant, and marine mammals in mainland Portugal and archipelagos of the Azores and Madeira that includes 105,026 data entries between 1873 and 2021 (72% of the data occurring in 2000 and 2021). The methods used to collect the data were: live observations/captures (43%), sign surveys (35%), camera trapping (16%), bioacoustics surveys (4%) and radiotracking, and inquiries that represent less than 1% of the records. The data set includes 13 types of records: (1) burrows | soil mounds | tunnel, (2) capture, (3) colony, (4) dead animal | hair | skulls | jaws, (5) genetic confirmation, (6) inquiries, (7) observation of live animal (8), observation in shelters, (9) photo trapping | video, (10) predators diet | pellets | pine cones/nuts, (11) scat | track | ditch, (12) telemetry and (13) vocalization | echolocation. The spatial uncertainty of most records ranges between 0 and 100 m (76%). Rodentia ( n =31,573) has the highest number of records followed by Chiroptera ( n = 18,857), Carnivora ( n = 18,594), Lagomorpha ( n = 17,496), Cetartiodactyla ( n = 11,568) and Eulipotyphla ( n = 7008). The data set includes records of species classified by the IUCN as threatened (e.g., Oryctolagus cuniculus [ n = 12,159], Monachus monachus [ n = 1,512], and Lynx pardinus [ n = 197]). We believe that this data set may stimulate the publication of other European countries data sets that would certainly contribute to ecology and conservation‐related research, and therefore assisting on the development of more accurate and tailored conservation management strategies for each species. There are no copyright restrictions; please cite this data paper when the data are used in publications.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Prevalence of genetically similar Flavobacterium columnare phages across aquaculture environments reveals a strong potential for pathogen control - Anniina Runtuvuori‐Salmela; Heidi M. T. Kunttu; Elina Laanto; Gabriel M. F. Almeida; Kati Mäkelä; Mathias Middelboe; Lotta‐Riina Sundberg (Environmental Microbiology, 2022)
Summary Intensive aquaculture conditions expose fish to bacterial infections, leading to significant financial losses, extensive antibiotic use and risk of antibiotic resistance in target bacteria. Flavobacterium columnare causes columnaris disease in aquaculture worldwide. To develop a bacteriophage‐based control of columnaris disease, we isolated and characterized 126 F . columnare strains and 63 phages against F . columnare from Finland and Sweden in 2017. Bacterial isolates were virulent on rainbow trout ( Oncorhynchus mykiss ) and fell into four previously described genetic groups A, C, E and G, with genetic groups C and E being the most virulent. Phage host range studied against a collection of 227 bacterial isolates (from 2013 to 2017) demonstrated modular infection patterns based on host genetic group. Phages infected contemporary and previously isolated bacterial hosts, but bacteria isolated most recently were generally resistant to previously isolated phages. Despite large differences in geographical origin, isolation year or host range of the phages, whole‐genome sequencing of 56 phages showed high level of genetic similarity to previously isolated F . columnare phages ( Ficleduovirus , Myoviridae ). Altogether, this phage collection demonstrates a potential for use in phage therapy.

Early post-discharge mortality in CAP: frequency, risk factors and a prediction tool - Verena Glöckner; Mathias W. Pletz; Gernot Rohde; Jan Rupp; Martin Witzenrath; Grit Barten-Neiner; Martin Kolditz; M. Dreher; C. Cornelissen; W. Knüppel; D. Stolz; N. Suttorp; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2022)
There are few data on mortality after discharge with community-acquired pneumonia (CAP). Therefore, we evaluated risk factors for 30-day post-discharge mortality after CAP. We included all patients of the prospective multi-national CAPNETZ study between 2002 and 2018 with (1) hospitalized CAP, (2) survival until discharge, and (3) complete follow-up data. The study endpoint was death within 30 days after discharge. We evaluated risk factors including demographics, comorbidities, admission CAP severity, and laboratory values and treatment-related factors in uni- and multivariable analyses. A total of 126 (1.6%) of 7882 included patients died until day 30 after discharge, corresponding to 26% of all 476 deaths. After multivariable analysis, we identified 10 independent risk factors: higher age, lower BMI, presence of diabetes mellitus, chronic renal or chronic neurological disease (other than cerebrovascular diseases), low body temperature or higher thrombocytes on admission, extended length of hospitalization, oxygen therapy during hospitalization, and post-obstructive pneumonia. By addition these factors, we calculated a risk score with an AUC of 0.831 (95%CI 0.822–0.839, p < 0.001) for prediction of post-discharge mortality. Early post-discharge deaths account for ¼ of all CAP-associated deaths and are associated with patient- and CAP-severity-related risk factors. Additional studies are necessary to replicate our findings in independent cohorts. Study registration: NCT 02139163.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

Cover Image - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)

A global agenda for advancing freshwater biodiversity research - Alain Maasri; Sonja C. Jähnig; Mihai C. Adamescu; Rita Adrian; Claudio Baigun; Donald J. Baird; Angelica Batista‐Morales; Núria Bonada; Lee E. Brown; Qinghua Cai; Joao V. Campos‐Silva; Viola Clausnitzer; et al. (Ecology Letters, 2022)
Global freshwater biodiversity is declining dramatically, and meeting the challenges of this crisis requires bold goals and the mobilisation of substantial resources. While the reasons are varied, investments in both research and conservation of freshwater biodiversity lag far behind those in the terrestrial and marine realms. Inspired by a global consultation, we identify 15 pressing priority needs, grouped into five research areas, in an effort to support informed stewardship of freshwater biodiversity. The proposed agenda aims to advance freshwater biodiversity research globally as a critical step in improving coordinated actions towards its sustainable management and conservation.

Climate change impacts plant carbon balance, increasing mean future carbon use efficiency but decreasing total forest extent at dry range edges - Justin M. Mathias; Anna T. Trugman (Ecology Letters, 2022)
Carbon use efficiency (CUE) represents how efficient a plant is at translating carbon gains through gross primary productivity (GPP) into net primary productivity (NPP) after respiratory costs ( R a ). CUE varies across space with climate and species composition, but how CUE will respond to climate change is largely unknown due to uncertainty in R a at novel high temperatures. We use a plant physiological model validated against global CUE observations and LIDAR vegetation canopy height data and find that model‐predicted decreases in CUE are diagnostic of transitions from forests to shrubland at dry range edges. Under future climate scenarios, we show mean growing season CUE increases in core forested areas, but forest extent decreases at dry range edges, with substantial uncertainty in absolute CUE due to uncertainty in R a . Our results highlight that future forest resilience is nuanced and controlled by multiple competing mechanisms.

Characterization of allelochemicals from Pistia stratiotes extracts and their effects on the growth and physiology of Microcystis aeruginosa - Anderson Lourenção; Gustavo F. Mecina; Micheline K. Cordeiro-Araújo; Maria C. Bittencourt-Oliveira; Mathias A. Chia; João L. Bronzel-Júnior; Filipe O. Granero; Luciana P. Silva; Regildo M. G. da Silva (Environmental Science and Pollution Research, 2021)

Disproportionate microbial responses to decadal drainage on a Siberian floodplain - Min Jung Kwon; Binu M. Tripathi; Mathias Göckede; Seung Chul Shin; Nu Ri Myeong; Yoo Kyung Lee; Mincheol Kim (Global Change Biology, 2021)
Permafrost thaw induces soil hydrological changes which in turn affects carbon cycle processes in the Arctic terrestrial ecosystems. However, hydrological impacts of thawing permafrost on microbial processes and greenhouse gas (GHG) dynamics are poorly understood. This study examined changes in microbial communities using gene and genome‐centric metagenomics on an Arctic floodplain subject to decadal drainage, and linked them to CO 2 and CH 4 flux and soil chemistry. Decadal drainage led to significant changes in the abundance, taxonomy, and functional potential of microbial communities, and these modifications well explained the changes in CO 2 and CH 4 fluxes between ecosystem and atmosphere—increased fungal abundances potentially increased net CO 2 emission rates and highly reduced CH 4 emissions in drained sites corroborated the marked decrease in the abundance of methanogens and methanotrophs. Interestingly, various microbial taxa disproportionately responded to drainage: Methanoregula , one of the key players in methanogenesis under saturated conditions, almost disappeared, and also Methylococcales methanotrophs were markedly reduced in response to drainage. Seven novel methanogen population genomes were recovered, and the metabolic reconstruction of highly correlated population genomes revealed novel syntrophic relationships between methanogenic archaea and syntrophic partners. These results provide a mechanistic view of microbial processes regulating GHG dynamics in the terrestrial carbon cycle, and disproportionate microbial responses to long‐term drainage provide key information for understanding the effects of warming‐induced soil drying on microbial processes in Arctic wetland ecosystems.

Correction to: Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Statistical upscaling of ecosystem CO 2 fluxes across the terrestrial tundra and boreal domain: Regional patterns and uncertainties - Anna‐Maria Virkkala; Juha Aalto; Brendan M. Rogers; Torbern Tagesson; Claire C. Treat; Susan M. Natali; Jennifer D. Watts; Stefano Potter; Aleksi Lehtonen; Marguerite Mauritz; Edward A. G. Schuur; John Kochendorfer; et al. (Global Change Biology, 2021)
The regional variability in tundra and boreal carbon dioxide (CO 2 ) fluxes can be high, complicating efforts to quantify sink‐source patterns across the entire region. Statistical models are increasingly used to predict (i.e., upscale) CO 2 fluxes across large spatial domains, but the reliability of different modeling techniques, each with different specifications and assumptions, has not been assessed in detail. Here, we compile eddy covariance and chamber measurements of annual and growing season CO 2 fluxes of gross primary productivity (GPP), ecosystem respiration (ER), and net ecosystem exchange (NEE) during 1990–2015 from 148 terrestrial high‐latitude (i.e., tundra and boreal) sites to analyze the spatial patterns and drivers of CO 2 fluxes and test the accuracy and uncertainty of different statistical models. CO 2 fluxes were upscaled at relatively high spatial resolution (1 km 2 ) across the high‐latitude region using five commonly used statistical models and their ensemble, that is, the median of all five models, using climatic, vegetation, and soil predictors. We found the performance of machine learning and ensemble predictions to outperform traditional regression methods. We also found the predictive performance of NEE‐focused models to be low, relative to models predicting GPP and ER. Our data compilation and ensemble predictions showed that CO 2 sink strength was larger in the boreal biome (observed and predicted average annual NEE −46 and −29 g C m −2 yr −1 , respectively) compared to tundra (average annual NEE +10 and −2 g C m −2 yr −1 ). This pattern was associated with large spatial variability, reflecting local heterogeneity in soil organic carbon stocks, climate, and vegetation productivity. The terrestrial ecosystem CO 2 budget, estimated using the annual NEE ensemble prediction, suggests the high‐latitude region was on average an annual CO 2 sink during 1990–2015, although uncertainty remains high.

Dynamics of Baltic Sea phages driven by environmental changes - Matthias Hoetzinger; Emelie Nilsson; Rahaf Arabi; Christofer M. G. Osbeck; Benjamin Pontiller; Geoffrey Hutinet; Oliver W. Bayfield; Sachia Traving; Veljo Kisand; Daniel Lundin; Jarone Pinhassi; Mathias Middelboe; et al. (Environmental Microbiology, 2021)
Summary Phage predation constitutes a major mortality factor for bacteria in aquatic ecosystems, and thus, directly impacts nutrient cycling and microbial community dynamics. Yet, the population dynamics of specific phages across time scales from days to months remain largely unexplored, which limits our understanding of their influence on microbial succession. To investigate temporal changes in diversity and abundance of phages infecting particular host strains, we isolated 121 phage strains that infected three bacterial hosts during a Baltic Sea mesocosm experiment. Genome analysis revealed a novel Flavobacterium phage genus harboring gene sets putatively coding for synthesis of modified nucleotides and glycosylation of bacterial cell surface components. Another novel phage genus revealed a microdiversity of phage species that was largely maintained during the experiment and across mesocosms amended with different nutrients. In contrast to the newly described Flavobacterium phages, phages isolated from a Rheinheimera strain were highly similar to previously isolated genotypes, pointing to genomic consistency in this population. In the mesocosm experiment, the investigated phages were mainly detected after a phytoplankton bloom peak. This concurred with recurrent detection of the phages in the Baltic Proper during summer months, suggesting an influence on the succession of heterotrophic bacteria associated with phytoplankton blooms.

Are visual working memory and episodic memory distinct processes? Insight from stroke patients by lesion-symptom mapping - Selma Lugtmeijer; Linda Geerligs; Frank Erik de Leeuw; Edward H. F. de Haan; Roy P. C. Kessels; Anouk R. Smits; Ben A. Schmand; Edward H. F. de Haan; Frank Erik de Leeuw; Gert jan Luijckx; H. Steven Scholte; Joke M. Spikman; et al. (Brain Structure and Function, 2021)
Working memory and episodic memory are two different processes, although the nature of their interrelationship is debated. As these processes are predominantly studied in isolation, it is unclear whether they crucially rely on different neural substrates. To obtain more insight in this, 81 adults with sub-acute ischemic stroke and 29 elderly controls were assessed on a visual working memory task, followed by a surprise subsequent memory test for the same stimuli. Multivariate, atlas- and track-based lesion-symptom mapping (LSM) analyses were performed to identify anatomical correlates of visual memory. Behavioral results gave moderate evidence for independence between discriminability in working memory and subsequent memory, and strong evidence for a correlation in response bias on the two tasks in stroke patients. LSM analyses suggested there might be independent regions associated with working memory and episodic memory. Lesions in the right arcuate fasciculus were more strongly associated with discriminability in working memory than in subsequent memory, while lesions in the frontal operculum in the right hemisphere were more strongly associated with criterion setting in subsequent memory. These findings support the view that some processes involved in working memory and episodic memory rely on separate mechanisms, while acknowledging that there might also be shared processes.

Spatial variability of prokaryotic and viral abundances in the Kermadec and Atacama Trench regions - Clemens Schauberger; Mathias Middelboe; Morten Larsen; Logan M. Peoples; Douglas H. Bartlett; Finn Kirpekar; Ashley A. Rowden; Frank Wenzhöfer; Bo Thamdrup; Ronnie N. Glud (Limnology and Oceanography, 2021)
Hadal trenches represent the deepest part of the ocean and are dynamic depocenters with intensified prokaryotic activity. Here, we explored the distribution and drivers of prokaryotic and viral abundance from the ocean surface and 40 cm into sediments in two hadal trench regions with contrasting surface productivity. In the water column, prokaryotic and viral abundance decreased with water depth before reaching a rather stable level at ~ 4000 m depth at both trench systems, while virus to prokaryote ratios were increasing with depth, presumably reflecting the declining availability of organic material. Prokaryotic and viral abundances in sediments were lower at the adjacent abyssal sites than at the hadal sites and declined exponentially with sediment depth, closely tracking the attenuation of total organic carbon (TOC) content. In contrast, hadal sediment exhibited erratic depth profiles of prokaryotes and viruses with many subsurface peaks. The prokaryotic abundance correlated well to extensive fluctuations in TOC content at centimeter scale, which were likely caused by recurring mass wasting events. Yet while prokaryotic and viral abundances cross correlated well in the abyssal sediments, there was no clear correlation in the hadal sites. The results suggested that dynamic depositional conditions and higher substrate availability result in a high spatial heterogeneity in viral and prokaryotic abundances in hadal sediments in comparison to more stable abyssal settings. We argue that these conditions enhance the relatively importance of viruses for prokaryotic mortality and carbon recycling in hadal settings.

Climate change reshapes the eco‐evolutionary dynamics of a Neotropical seed dispersal system - Lilian P. Sales; W. Daniel Kissling; Mauro Galetti; Babak Naimi; Mathias M. Pires (Global Ecology and Biogeography, 2021)
Aim Global changes will redistribute biodiversity, reshaping ecological interactions and ecosystem processes. The decoupling in the distribution of plants and their mutualistic seed dispersers, for instance, may have overlooked eco‐evolutionary effects. How animal‐dispersed plants will respond to changes in the distribution of their seed dispersers remains largely an open question. Here, we forecast the consequences of climate change and frugivory interactions for the spatial distribution and seed size evolution of a Neotropical palm species. Location Atlantic forests of South America. Time period Present day, end of 21st century. Major taxa studied Thirty‐two species of frugivorous birds, and a palm ( Euterpe edulis ). Methods Future patterns of animal–plant co‐occurrence were derived from ecological niche models, climate forecasts, projections of future forest loss, and seed dispersal simulations. We further explored the evolutionary effect of the spatial reorganization of interactions by modelling palm seed sizes as a function of changes in the distribution of frugivore traits. Results Our models indicate that future climate change and deforestation may reduce the palm’s suitable distribution by 20%–50%. However, our simulations suggest that 66% of all remaining future suitable distribution (76,200 km 2 ) would still be inaccessible to the palm without the active dispersal of seeds by frugivores. In addition, novel frugivore communities are projected to have smaller mean body mass and gape size (−23% and −10%, respectively), due to the loss of large frugivores, which may translate into a 6%–17% reduction of seed sizes across the palm’s remaining distribution. Main conclusions Our projections indicate that frugivore seed dispersal may be critical to allow occupancy of future habitat by animal‐dispersed plants. However, loss of large frugivores may affect trait selection regimes, creating hotspots of plant evolution towards smaller seeds. We argue that such complex dynamics emerging from species‐specific responses to global change may reshape the distribution and evolution of several interacting partners worldwide.

Effect of the hydroxamate group in the antitumoral activity and toxicity toward normal cells of new copper(II) complexes - Nathália F. B. Azeredo; Franz V. Borges; Marcelo S. Mathias; Jackson A. L. C. Resende; Roberto W. A. Franco; Milton M. Kanashiro; Adolfo Horn; Christiane Fernandes (BioMetals, 2021)

Forest responses to last‐millennium hydroclimate variability are governed by spatial variations in ecosystem sensitivity - Christine R. Rollinson; Andria Dawson; Ann M. Raiho; John W. Williams; Michael C. Dietze; Thomas Hickler; Stephen T. Jackson; Jason McLachlan; David JP Moore; Benjamin Poulter; Tristan Quaife; Jörg Steinkamp; et al. (Ecology Letters, 2021)
Forecasts of future forest change are governed by ecosystem sensitivity to climate change, but ecosystem model projections are under‐constrained by data at multidecadal and longer timescales. Here, we quantify ecosystem sensitivity to centennial‐scale hydroclimate variability, by comparing dendroclimatic and pollen‐inferred reconstructions of drought, forest composition and biomass for the last millennium with five ecosystem model simulations. In both observations and models, spatial patterns in ecosystem responses to hydroclimate variability are strongly governed by ecosystem sensitivity rather than climate exposure. Ecosystem sensitivity was higher in models than observations and highest in simpler models. Model‐data comparisons suggest that interactions among biodiversity, demography and ecophysiology processes dampen the sensitivity of forest composition and biomass to climate variability and change. Integrating ecosystem models with observations from timescales extending beyond the instrumental record can better understand and forecast the mechanisms regulating forest sensitivity to climate variability in a complex and changing world.

Reproductive biology of the anchovy (Stolephorus commersonnii, Lacepède, 1803) and spotted sardine (Amblygaster sirm, Walbaum, 1792) from Tanga Region, Tanzania - Joseph S. Sululu; Albogast T. Kamukuru; Baraka C. Sekadende; Shigalla B. Mahongo; Mathias M. Igulu (Western Indian Ocean Journal of Marine Science, 2021)
The present study investigated the reproductive biology of Stolephorus commersonnii and Amblygaster sirm at two landing sites in Tanga on the northern coast of Tanzania. Fish samples were collected on a monthly basis from ringnets operated by artisanal fishers in the nearby coastal waters. Spawning seasons were determined using gonadosomatic index (GSI) and gonadal maturity stages. The size at first maturity was 57.7 mm and 66.2 mm total length for male and female S. commersonnii respectively. Male and female A. sirm were estimated to attain first maturity at 147.7 mm and 169.2 mm respectively. The spawning seasons of both species were protracted. S. commersonnii demonstrated a year round spawning cycle with peaks in August, October and January. The peak spawning season for male and female A. sirm was recorded in August and September respectively. Both species exhibited skewed size-dependent sex ratios with females predominating in the larger size classes. A. sirm had a higher fecundity rate with a maximum of 96,500 eggs in the largest female fish of 258 mm as compared to S. commersonnii (10,055 eggs) in the largest fish of 98 mm. The mean (±SE) total fecundity of S. comersonnii and A. sirm was 5,134.7 ± 136.9 eggs, and 47,029.03 ± 1,435.13 eggs in females of sizes 68 mm to 98 mm and 170 mm to 258 mm respectively.

Preliminary findings on the food and feeding dynamics of the anchovy Stolephorus commersonnii (Lacepède, 1803) and the Indian mackerel Rastrelliger kanagurta (Cuvier, 1817) from Tanga Region, Tanzania - Baraka C. Sekadende; Joseph S. Sululu; Albogast T. Kamukuru; Mathias M. Igulu; Shigalla B. Mahongo (Western Indian Ocean Journal of Marine Science, 2021)
Small pelagic fishes play an important role in the ecosystem by linking planktonic production and higher trophic level predators, and provide a livelihood to both the small-scale and commercial fisher communities. This study analyzed the food and feeding habits of Stolephorus commersonnii (Lacepède, 1803) and Rastrelliger kanagurta (Cuvier, 1817) from the ring-net fishery in Tanga, Tanzania. A total of 1 434 and 320 stomachs of S. commersonnii and R. kanagurta respectively were examined for gut contents using the relative volumetric method. S. commersonnii was found to be a planktivorous carnivore, feeding principally on planktonic penaeid shrimps (48.6%), fish larvae (33.2%) and zooplankton (12.3%). R. kanagurta was found to be carnivorous, feeding predominantly on fish (60.6%), mainly S. commersonnii, while penaeid shrimps, juvenile fish, and juvenile stages of squids formed 26.5% of the total number of food items in R. kanagurta guts. Both S. commersonnii and R. kanagurta exhibited ontogenic diet shifts, where they fed exclusively on small prey as juveniles and consumed larger food items as they grew. The index of vacuity was higher in S. commersonnii (46.1%) than in R. kanagurta (16.6%). This study revealed the importance of penaeid shrimps as food for S. commersonnii, that in turn formed the main food for R. kanagurta. This implied that the two species were able to coexist in the same niche by avoiding interspecific competition for food.

Extreme Levels of Ocean Acidification Restructure the Plankton Community and Biogeochemistry of a Temperate Coastal Ecosystem: A Mesocosm Study - Carsten Spisla; Jan Taucher; Lennart T. Bach; Mathias Haunost; Tim Boxhammer; Andrew L. King; Bettany D. Jenkins; Joselynn R. Wallace; Andrea Ludwig; Jana Meyer; Paul Stange; Fabrizio Minutolo; et al. (Frontiers in Marine Science, 2021)
The oceans’ uptake of anthropogenic carbon dioxide (CO 2 ) decreases seawater pH and alters the inorganic carbon speciation – summarized in the term ocean acidification (OA). Already today, coastal regions experience episodic pH events during which surface layer pH drops below values projected for the surface ocean at the end of the century. Future OA is expected to further enhance the intensity of these coastal extreme pH events. To evaluate the influence of such episodic OA events in coastal regions, we deployed eight pelagic mesocosms for 53 days in Raunefjord, Norway, and enclosed 56–61 m 3 of local seawater containing a natural plankton community under nutrient limited post-bloom conditions. Four mesocosms were enriched with CO 2 to simulate extreme p CO 2 levels of 1978 – 2069 μatm while the other four served as untreated controls. Here, we present results from multivariate analyses on OA-induced changes in the phyto-, micro-, and mesozooplankton community structure. Pronounced differences in the plankton community emerged early in the experiment, and were amplified by enhanced top-down control throughout the study period. The plankton groups responding most profoundly to high CO 2 conditions were cyanobacteria (negative), chlorophyceae (negative), auto- and heterotrophic microzooplankton (negative), and a variety of mesozooplanktonic taxa, including copepoda (mixed), appendicularia (positive), hydrozoa (positive), fish larvae (positive), and gastropoda (negative). The restructuring of the community coincided with significant changes in the concentration and elemental stoichiometry of particulate organic matter. Results imply that extreme CO 2 events can lead to a substantial reorganization of the planktonic food web, affecting multiple trophic levels from phytoplankton to primary and secondary consumers.

Efficacy of carvacrol on Rhipicephalus (Boophilus) microplus engorged female ticks (Canestrini, 1887) (Acari: Ixodidae): effects on mortality and reproduction - Amilcar Machado Pereira Junior; M. I. Camargo-Mathias; E. Daemon; A. P. Peconick; J. R. Lima-Souza; P. R. Oliveira; A. S. Braga; L. J. Lara; R. N. Remedio (Natural Product Research, 2020)

Biobanking in amphibian and reptilian conservation and management: opportunities and challenges - Julie Strand; Helena Thomsen; Julie B. Jensen; Cecilie Marcussen; Trine B. Nicolajsen; Mathias B. Skriver; Isabella M. Søgaard; Tariq Ezaz; Stig Purup; Henrik Callesen; Cino Pertoldi (Conservation Genetics Resources, 2020)

Climate and land‐use change will lead to a faunal “savannization” on tropical rainforests - Lilian P. Sales; Mauro Galetti; Mathias M. Pires (Global Change Biology, 2020)
Humans have fragmented, reduced or altered the biodiversity in tropical forests around the world. Climate and land‐use change act synergistically, increasing drought and fire frequencies, converting several tropical rainforests into derived savannas, a phenomenon known as “savannization.” Yet, we lack a full understanding of the faunal changes in response to the transformation of plant communities. We argue that the composition of vertebrate assemblages in ecotone regions of forest–savanna transitions from South America will be increasingly replaced by open savanna species, a phenomenon we name “faunal savannization.” We combined projections from ecological niche models, habitat filter masks and dispersal simulations to forecast the distribution of 349 species of forest‐ and savanna‐dwelling mammal species across South America. We found that the distribution of savanna species is likely to increase by 11%–30% and spread over lowland Amazon and Atlantic forests. Conversely, forest‐specialists are expected to lose nearly 50% of their suitable ranges and to move toward core forest zones, which may thus receive an influx of more than 60 species on the move. Our findings indicate that South American ecotonal faunas might experience high rates of occupancy turnover, in a process parallel to that already experienced by plants. Climate‐driven migrations of fauna in human‐dominated landscapes will likely interact with fire‐induced changes in plant communities to reshape the biodiversity in tropical rainforests worldwide.

Introduced marine ecosystem engineer indirectly affects parasitism in native mussel hosts - M. Anouk Goedknegt; Christian Buschbaum; Jaap van der Meer; K. Mathias Wegner; David W. Thieltges (Biological Invasions, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

Spread of the invasive shell-boring annelid Polydora websteri (Polychaeta, Spionidae) into naturalised oyster reefs in the European Wadden Sea - Andreas M. Waser; Dagmar Lackschewitz; Jeffrey Knol; Karsten Reise; K. Mathias Wegner; David W. Thieltges (Marine Biodiversity, 2020)
With globally growing aquaculture activities, the co-introduction of parasites alongside large-scale movements of commercial species poses an increasing risk for marine ecosystems. Here, we present the first record of the shell-boring polychaete Polydora websteri Hartman in Loosanoff and Engle, 1943 in invasive Pacific oysters Crassostrea ( Magallana ) gigas (Thunberg, 1793) in the European Atlantic Ocean. In October 2014, mud blisters in the shells of wild Pacific oysters and specimens of a spionid polychaete were observed in close proximity to a commercial oyster farm at the island of Sylt (Germany) in the European Wadden Sea. Subsequent investigations indicated that these blisters only occurred near the farm and that no other mollusc species were affected. Morphological and molecular analysis identified the polychaete as Polydora websteri , a species that nowadays widely occurs around the globe, but likely is native to the Asian Pacific. Later sampling activities detected P. websteri also at other locations around Sylt as well as in the Dutch part of the Wadden Sea at the island of Texel. The number of polychaetes in the oysters was, however, relatively low and mostly below 10 individuals per oyster. Together, this evidence suggests that P. websteri is currently extending its range. As the introduction of P. websteri may have severe ecological and economic implications, this study aims to alert others to look for P. websteri at Western European coasts within farmed or wild Pacific oysters to further document its spread.

Bacterial etiology of community-acquired pneumonia in immunocompetent hospitalized patients and appropriateness of empirical treatment recommendations: an international point-prevalence study - Manuela Carugati; S. Aliberti; G. Sotgiu; F. Blasi; A. Gori; R. Menendez; M. Encheva; M. Gallego; P. Leuschner; S. Ruiz-Buitrago; S. Battaglia; R. Fantini; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

A global perspective on the climate‐driven growth synchrony of neighbouring trees - Ernesto Tejedor; Roberto Serrano‐Notivoli; Martin de Luis; Miguel Angel Saz; Claudia Hartl; Scott St. George; Ulf Büntgen; Andrew M. Liebhold; Mathias Vuille; Jan Esper (Global Ecology and Biogeography, 2020)
Aim Previous work demonstrated the global variability of synchrony in tree growth within populations, that is, the covariance of the year‐to‐year variability in growth of individual neighbouring trees. However, there is a lack of knowledge about the causes of this variability and its trajectories through time. Here, we examine whether climate can explain variation in within‐population synchrony (WPS) across space but also through time and we develop models capable of explaining this variation. These models can be applied to the global tree cover under current and future climate change scenarios. Location Global. Time period 1901–2012. Major taxa studied Trees. Methods We estimated WPS values from a global tree‐ring width database consisting of annual growth increment measurements from multiple trees at 3,579 sites. We used generalized linear mixed effects models to infer the drivers of WPS variability and temporal trends of global WPS. We then predicted WPS values across the global extent of tree cover. Finally, we applied our model to predict future WPS based on the RCP 8.5 (2045–2065 period) emission scenario. Results Areas with the highest WPS are characterized by a combination of environments with both high mean annual temperature (>10°C) and low precipitation ( Main conclusions Climate explains WPS variability in space and time. We suggest that WPS might have value as an integrative ecological measure of the level of environmental stress to which forests are subjected and therefore holds potential for diagnosing effects of global climate change on tree growth.

The indirect paths to cascading effects of extinctions in mutualistic networks - Mathias M. Pires; James L. O'Donnell; Laura A. Burkle; Cecilia Díaz‐Castelazo; David H. Hembry; Justin D. Yeakel; Erica A. Newman; Lucas P. Medeiros; Marcus A. M. de Aguiar; Paulo R. Guimarães (Ecology, 2020)
Biodiversity loss is a hallmark of our times, but predicting its consequences is challenging. Ecological interactions form complex networks with multiple direct and indirect paths through which the impacts of an extinction may propagate. Here we show that accounting for these multiple paths connecting species is necessary to predict how extinctions affect the integrity of ecological networks. Using an approach initially developed for the study of information flow, we estimate indirect effects in plant–pollinator networks and find that even those species with several direct interactions may have much of their influence over others through long indirect paths. Next, we perform extinction simulations in those networks and show that although traditional connectivity metrics fail in the prediction of coextinction patterns, accounting for indirect interaction paths allows predicting species’ vulnerability to the cascading effects of an extinction event. Embracing the structural complexity of ecological systems contributes towards a more predictive ecology, which is of paramount importance amid the current biodiversity crisis.

Klotho Is Neuroprotective in the Superoxide Dismutase (SOD1G93A) Mouse Model of ALS - Ella Zeldich; Ci-Di Chen; Emma Boden; Bryce Howat; Jason S. Nasse; Dean Zeldich; Anthony G. Lambert; Andrea Yuste; Jonathan D. Cherry; Rebecca M. Mathias; Qicheng Ma; Nelson C. Lau; et al. (Journal of Molecular Neuroscience, 2019)

Renin cells with defective Gsα/cAMP signaling contribute to renal endothelial damage - Anne Steglich; Friederike Kessel; Linda Hickmann; Michael Gerlach; Peter Lachmann; Florian Gembardt; Mathias Lesche; Andreas Dahl; Anna Federlein; Frank Schweda; Christian P. M. Hugo; Vladimir T. Todorov (Pflügers Archiv - European Journal of Physiology, 2019)

Foot-and-mouth disease in Southern Ghana: occurrence and molecular characterization of circulating viruses - Mathias V. Teye; Teresa K. Sebunya; Elliot M. Fana; Donald P. King; LaToya Seoke; Nick J. Knowles; Joseph A. Awuni; George Matlho; Melvin Leteane; Joseph M. K. Hyera (Tropical Animal Health and Production, 2019)

Rise Up, Get Tested, and Live: an Arts-Based Colorectal Cancer Educational Program in a Faith-Based Setting - Daniela B. Friedman; Swann Arp Adams; Heather M. Brandt; Sue P. Heiney; James R. Hébert; John R. Ureda; Jessica S. Seel; Courtney S. Schrock; Wilhelmenia Mathias; Vivian Clark-Armstead; Reverend Vernette Dees; Reverend Perry Oliver (Journal of Cancer Education, 2019)

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

How invasive oysters can affect parasite infection patterns in native mussels on a large spatial scale - M. Anouk Goedknegt; Reinier Nauta; Mirjana Markovic; Christian Buschbaum; Eelke O. Folmer; Pieternella C. Luttikhuizen; Jaap van der Meer; Andreas M. Waser; K. Mathias Wegner; David W. Thieltges (Oecologia, 2019)

Drainage enhances modern soil carbon contribution but reduces old soil carbon contribution to ecosystem respiration in tundra ecosystems - Min Jung Kwon; Susan M. Natali; Caitlin E. Hicks Pries; Edward A. G. Schuur; Axel Steinhof; K. Grace Crummer; Nikita Zimov; Sergey A. Zimov; Martin Heimann; Olaf Kolle; Mathias Göckede (Global Change Biology, 2019)
Warming temperatures are likely to accelerate permafrost thaw in the Arctic, potentially leading to the release of old carbon previously stored in deep frozen soil layers. Deeper thaw depths in combination with geomorphological changes due to the loss of ice structures in permafrost, may modify soil water distribution, creating wetter or drier soil conditions. Previous studies revealed higher ecosystem respiration rates under drier conditions, and this study investigated the cause of the increased ecosystem respiration rates using radiocarbon signatures of respired CO 2 from two drying manipulation experiments: one in moist and the other in wet tundra. We demonstrate that higher contributions of CO 2 from shallow soil layers (0–15 cm; modern soil carbon) drive the increased ecosystem respiration rates, while contributions from deeper soil (below 15 cm from surface and down to the permafrost table; old soil carbon) decreased. These changes can be attributed to more aerobic conditions in shallow soil layers, but also the soil temperature increases in shallow layers but decreases in deep layers, due to the altered thermal properties of organic soils. Decreased abundance of aerenchymatous plant species following drainage in wet tundra reduced old carbon release but increased aboveground plant biomass elevated contributions of autotrophic respiration to ecosystem respiration. The results of this study suggest that drier soils following drainage may accelerate decomposition of modern soil carbon in shallow layers but slow down decomposition of old soil carbon in deep layers, which may offset some of the old soil carbon loss from thawing permafrost.

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data - Karen Y. He; Xiaoyin Li; Tanika N. Kelly; Jingjing Liang; Brian E. Cade; Themistocles L. Assimes; Lewis C. Becker; Amber L. Beitelshees; Adam P. Bress; Yen-Pei Christy Chang; Yii-Der Ida Chen; Paul S. de Vries; et al. (Human Genetics, 2019)

The role of competition in driving species global distributions: Soricid shrews as a case study - Tomé Neves; Joaquim T. Tapisso; Miguel Porto; Henrique M. Pereira; Maria L. Mathias; Luís Borda‐de‐Água (Journal of Biogeography, 2019)
Aim We aim to determine the relative influence of climate and species interactions on the global distribution of Soricinae and Crocidurinae shrews through the analysis of their distribution, climate niche and evolutionary history. Both subfamilies are partially allopatric in Eurasia, but in North America only Soricinae is present, thus providing a scenario to address the role of potential competition versus competitive release in determining species’ realized distributions at a global scale. Location Global. Taxon Soricidae, Eulipotyphla. Methods We obtained climate data from WorldClim, spatial range data for 302 species from the IUCN Red List and 2614 cytb complete sequences from GenBank. We modelled the potential distribution of the subfamilies by computing three environmental niche models using Maxent : one for Crocidurinae, one for American Soricinae and one for Afro‐Eurasian Soricinae. We created matrices for the genetic, spatial and climatic distance between all pairs of species to calculate the average climatic distance between pairs of species within and between subfamilies. We then evaluated this distance against a null model. To assess the effect of phylogeny on the segregation of the subfamilies, we checked for correlation between genetic and spatial distance. Results The Afro‐Eurasian Soricinae environmental niche model under‐predicted its occurrence in America. The average climatic distance between subfamilies was larger than expected by chance, while the distance within both Crocidurinae and Afro‐Eurasian Soricinae was smaller. The average distance between the American and Afro‐Eurasian Soricinae was also larger than expected. There was no correlation between spatial and genetic distance for genetic distances over 0.14 substitutions per nucleotide site. Main conclusions Climate significantly influences the distribution of both subfamilies. As expected in a scenario of competitive release, the climatic range of the Soricinae in America is larger than in Afro‐Eurasia. Thus, besides climate, competition may play an important role in shaping species’ global distributions.

Imaging Reporter Strategy to Monitor Gene Activation of Microglia Polarisation States under Stimulation - Franziska M. Collmann; Rory Pijnenburg; Gabriele Schneider; Cordula Schäfer; Kat Folz-Donahue; Christian Kukat; Mathias Hoehn (Journal of Neuroimmune Pharmacology, 2018)

Disentangling the effects of acidic air pollution, atmospheric CO 2 , and climate change on recent growth of red spruce trees in the Central Appalachian Mountains - Justin M. Mathias; Richard B. Thomas (Global Change Biology, 2018)
In the 45 years after legislation of the Clean Air Act, there has been tremendous progress in reducing acidic air pollutants in the eastern United States, yet limited evidence exists that cleaner air has improved forest health. Here, we investigate the influence of recent environmental changes on the growth and physiology of red spruce ( Picea rubens Sarg.) trees, a key indicator species of forest health, spanning three locations along a 100 km transect in the Central Appalachian Mountains. We incorporated a multiproxy approach using 75‐year tree ring chronologies of basal tree growth, carbon isotope discrimination (∆ 13 C, a proxy for leaf gas exchange), and δ 15 N (a proxy for ecosystem N status) to examine tree and ecosystem level responses to environmental change. Results reveal the two most important factors driving increased tree growth since ca . 1989 are reductions in acidic sulfur pollution and increases in atmospheric CO 2 , while reductions in pollutant emissions of NO x and warmer springs played smaller, but significant roles. Tree ring ∆ 13 C signatures increased significantly since 1989, concurrently with significant declines in tree ring δ 15 N signatures. These isotope chronologies provide strong evidence that simultaneous changes in C and N cycling, including greater photosynthesis and stomatal conductance of trees and increases in ecosystem N retention, were related to recent increases in red spruce tree growth and are consequential to ecosystem recovery from acidic pollution. Intrinsic water use efficiency ( i WUE ) of the red spruce trees increased by ~51% across the 75‐year chronology, and was driven by changes in atmospheric CO 2 and acid pollution, but i WUE was not linked to recent increases in tree growth. This study documents the complex environmental interactions that have contributed to the recovery of red spruce forest ecosystems from pervasive acidic air pollution beginning in 1989, about 15 years after acidic pollutants started to decline in the United States.

Coupling biogeochemical process rates and metagenomic blueprints of coastal bacterial assemblages in the context of environmental change - Trine Markussen; Elisabeth M. Happel; Jonna E. Teikari; Vimala Huchaiah; Johannes Alneberg; Anders F. Andersson; Kaarina Sivonen; Lasse Riemann; Mathias Middelboe; Veljo Kisand (Environmental Microbiology, 2018)
Summary Bacteria are major drivers of biogeochemical nutrient cycles and energy fluxes in marine environments, yet how bacterial communities respond to environmental change is not well known. Metagenomes allow examination of genetic responses of the entire microbial community to environmental change. However, it is challenging to link metagenomes directly to biogeochemical process rates. Here, we investigate metagenomic responses in natural bacterioplankton communities to simulated environmental stressors in the Baltic Sea, including increased river water input, increased nutrient concentration, and reduced oxygen level. This allowed us to identify informative prokaryotic gene markers, responding to environmental perturbation. Our results demonstrate that metagenomic and metabolic changes in bacterial communities in response to environmental stressors are influenced both by the initial community composition and by the biogeochemical factors shaping the functional response. Furthermore, the different sources of dissolved organic matter (DOM) had the largest impact on metagenomic blueprint. Most prominently, changes in DOM loads influenced specific transporter types reflecting the substrate availability and DOC assimilation and consumption pathways. The results provide new knowledge for developing models of ecosystem structure and biogeochemical cycling in future climate change scenarios and advance our exploration of the potential use of marine microorganisms as markers for environmental conditions.

The Impact of Three-Dimensional Effects on the Simulation of Turbulence Kinetic Energy in a Major Alpine Valley - Brigitta Goger; Mathias W. Rotach; Alexander Gohm; Oliver Fuhrer; Ivana Stiperski; Albert A. M. Holtslag (Boundary-Layer Meteorology, 2018)
The correct simulation of the atmospheric boundary layer (ABL) is crucial for reliable weather forecasts in truly complex terrain. However, common assumptions for model parametrizations are only valid for horizontally homogeneous and flat terrain. Here, we evaluate the turbulence parametrization of the numerical weather prediction model COSMO with a horizontal grid spacing of $$Δ x = 1.1\,\hbox {km}$$ Δ x = 1.1 km for the Inn Valley, Austria. The long-term, high-resolution turbulence measurements of the i-Box measurement sites provide a useful data pool of the ABL structure in the valley and on slopes. We focus on days and nights when ABL processes dominate and a thermally-driven circulation is present. Simulations are performed for case studies with both a one-dimensional turbulence parametrization, which only considers the vertical turbulent exchange, and a hybrid turbulence parametrization, also including horizontal shear production and advection in the budget of turbulence kinetic energy (TKE). We find a general underestimation of TKE by the model with the one-dimensional turbulence parametrization. In the simulations with the hybrid turbulence parametrization, the modelled TKE has a more realistic structure, especially in situations when the TKE production is dominated by shear related to the afternoon up-valley flow, and during nights, when a stable ABL is present. The model performance also improves for stations on the slopes. An estimation of the horizontal shear production from the observation network suggests that three-dimensional effects are a relevant part of TKE production in the valley.

BioTIME: A database of biodiversity time series for the Anthropocene - Maria Dornelas; Laura H. Antão; Faye Moyes; Amanda E. Bates; Anne E. Magurran; Dušan Adam; Asem A. Akhmetzhanova; Ward Appeltans; José Manuel Arcos; Haley Arnold; Narayanan Ayyappan; Gal Badihi; et al. (Global Ecology and Biogeography, 2018)
Motivation The BioTIME database contains raw data on species identities and abundances in ecological assemblages through time. These data enable users to calculate temporal trends in biodiversity within and amongst assemblages using a broad range of metrics. BioTIME is being developed as a community‐led open‐source database of biodiversity time series. Our goal is to accelerate and facilitate quantitative analysis of temporal patterns of biodiversity in the Anthropocene. Main types of variables included The database contains 8,777,413 species abundance records, from assemblages consistently sampled for a minimum of 2 years, which need not necessarily be consecutive. In addition, the database contains metadata relating to sampling methodology and contextual information about each record. Spatial location and grain BioTIME is a global database of 547,161 unique sampling locations spanning the marine, freshwater and terrestrial realms. Grain size varies across datasets from 0.0000000158 km 2 (158 cm 2 ) to 100 km 2 (1,000,000,000,000 cm 2 ). Time period and grain BioTIME records span from 1874 to 2016. The minimal temporal grain across all datasets in BioTIME is a year. Major taxa and level of measurement BioTIME includes data from 44,440 species across the plant and animal kingdoms, ranging from plants, plankton and terrestrial invertebrates to small and large vertebrates. Software format .csv and .SQL.

EFO-LCI: A New Life Cycle Inventory Database of Forestry Operations in Europe - Giuseppe Cardellini; Tatiana Valada; Claire Cornillier; Estelle Vial; Marian Dragoi; Venceslas Goudiaby; Volker Mues; Bruno Lasserre; Arkadiusz Gruchala; Per Kristian Rørstad; Mathias Neumann; Miroslav Svoboda; et al. (Environmental Management, 2018)

Service Lifetime, Storage Time, and Disposal Pathways of Electronic Equipment: A Swiss Case Study - Esther Thiébaud (‐Müller); Lorenz M. Hilty; Mathias Schluep; Rolf Widmer; Martin Faulstich (Journal of Industrial Ecology, 2018)
Summary Product lifetime is an essential aspect of dynamic material flow analyses and has been modeled using lifetime distribution functions, mostly average lifetimes. Existing data regarding the lifetime of electronic equipment (EE) are based on diverging definitions of lifetime as well as different temporal and regional scopes. After its active use, EE is often not disposed of immediately, but remains in storage for some time. Specific data on the share of EE that is stored and the time they remain in storage are scarce. This article investigates the service lifetime, storage time, and disposal pathways of ten electronic device types, based on data from an online survey complemented by structured interviews. We distinguish between new and secondhand devices and compute histograms, averages, and medians of the different lifetimes and their change over time. The average service lifetime varies from 3.3 years for mobile phones to 10.8 years for large loudspeakers, the average storage time from 0.8 years for flat panel display televisions to 3.6 years for large loudspeakers. Most service lifetime histograms are positively skewed and show substantial differences among device types. The storage time histograms, being more similar to one another, indicate that the storage behavior is similar for most device types. The data on disposal pathways show that a large proportion of devices are stored and reused before they reach the collection scheme.

The Oxygen Paradox, the French Paradox, and age-related diseases - Joanna M. S. Davies; Josiane Cillard; Bertrand Friguet; Enrique Cadenas; Jean Cadet; Rachael Cayce; Andrew Fishmann; David Liao; Anne-Laure Bulteau; Frédéric Derbré; Amélie Rébillard; Steven Burstein; et al. (GeroScience, 2017)

Glycoprotein-G-gene-based molecular and phylogenetic analysis of rabies viruses associated with a large outbreak of bovine rabies in southern Brazil - Juliana F. Cargnelutti; João M. de Quadros; Mathias Martins; Helena B. C. R. Batista; Rudi Weiblen; Eduardo F. Flores (Archives of Virology, 2017)

Ischemic Post-Conditioning Induces Post-Stroke Neuroprotection via Hsp70-Mediated Proteasome Inhibition and Facilitates Neural Progenitor Cell Transplantation - Thorsten R. Doeppner; Maria Doehring; Britta Kaltwasser; Arshad Majid; Fengyan Lin; Mathias Bähr; Ertugrul Kilic; Dirk M. Hermann (Molecular Neurobiology, 2017)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Acute and chronic treatment with quetiapine induces antidepressant-like behavior and exerts antioxidant effects in the rat brain - Zuleide M. Ignácio; Gislaine Z. Réus; Helena M. Abelaira; Airam B. de Moura; Thays G. de Souza; Danyela Matos; Mariana P. Goldim; Khiany Mathias; Leandro Garbossa; Fabricia Petronilho; João Quevedo (Metabolic Brain Disease, 2017)

Conditioned Medium Derived from Neural Progenitor Cells Induces Long-term Post-ischemic Neuroprotection, Sustained Neurological Recovery, Neurogenesis, and Angiogenesis - Thorsten R. Doeppner; Viktorija Traut; Alexander Heidenreich; Britta Kaltwasser; Bert Bosche; Mathias Bähr; Dirk M. Hermann (Molecular Neurobiology, 2017)

Glycerol metabolism and transport in yeast and fungi: established knowledge and ambiguities - Mathias Klein; Steve Swinnen; Johan M. Thevelein; Elke Nevoigt (Environmental Microbiology, 2017)
Summary There is huge variability among yeasts with regard to their efficiency in utilizing glycerol as the sole source of carbon and energy. Certain species show growth rates with glycerol comparable to those reached with glucose as carbon source; others are virtually unable to utilize glycerol, especially in synthetic medium. Most of our current knowledge regarding glycerol uptake and catabolic pathways has been gained from studying laboratory strains of the model yeast Saccharomyces cerevisiae . The growth of these strains on glycerol is dependent on the presence of medium supplements such as amino acids and nucleobases. In contrast, there is only fragmentary knowledge about S. cerevisiae isolates able to grow in synthetic glycerol medium without such supplements as well as about growth of non‐ Saccharomyces yeast species on glycerol. Thus, more research is required to understand why certain strains and species show superior growth performance on glycerol compared with common S. cerevisiae laboratory strains. This mini‐review summarizes what is known so far about the gene products and pathways involved in glycerol metabolism and transport in yeast and fungi as well as the regulation of these processes.

Spillover but no spillback of two invasive parasitic copepods from invasive Pacific oysters (Crassostrea gigas) to native bivalve hosts - M. Anouk Goedknegt; Anne-Karin Schuster; Christian Buschbaum; René Gergs; A. Sarina Jung; Pieternella C. Luttikhuizen; Jaap van der Meer; Karin Troost; K. Mathias Wegner; David W. Thieltges (Biological Invasions, 2017)

Dynamic Modulation of Microglia/Macrophage Polarization by miR-124 after Focal Cerebral Ischemia - Somayyeh Hamzei Taj; Widuri Kho; Markus Aswendt; Franziska M. Collmann; Claudia Green; Joanna Adamczak; Annette Tennstaedt; Mathias Hoehn (Journal of Neuroimmune Pharmacology, 2016)

Antimicrobial binding and growth kinetics in BacT/ALERT® FA Plus and BACTEC® Aerobic/F Plus blood culture media - D. Lovern; B. Katzin; K. Johnson; D. Broadwell; E. Miller; A. Gates; P. Deol; K. Doing; A. van Belkum; C. Marshall; E. Mathias; W. M. Dunne (European Journal of Clinical Microbiology & Infectious Diseases, 2016)

Site-level importance of broadleaf deciduous trees outweighs the legacy of high nitrogen (N) deposition on ecosystem N status of Central Appalachian red spruce forests - Kenneth R. Smith; Justin M. Mathias; Brenden E. McNeil; William T. Peterjohn; Richard B. Thomas (Plant and Soil, 2016)

High genetic structuring of Tula hantavirus - Sabrina Schmidt; Moritz Saxenhofer; Stephan Drewes; Mathias Schlegel; Konrad M. Wanka; Raphael Frank; Sven Klimpel; Felix von Blanckenhagen; Denny Maaz; Christiane Herden; Jona Freise; Ronny Wolf; et al. (Archives of Virology, 2016)

Effects of food and CO2 on growth dynamics of polyps of two scyphozoan species (Cyanea capillata and Chrysaora hysoscella) - Thomas J. Lesniowski; Maria Gambill; Sabine Holst; Myron A. Peck; María Algueró-Muñiz; Mathias Haunost; Arne M. Malzahn; Maarten Boersma (Marine Biology, 2015)

Ecosystem properties of semiarid savanna grassland in West Africa and its relationship with environmental variability - Torbern Tagesson; Rasmus Fensholt; Idrissa Guiro; Mads Olander Rasmussen; Silvia Huber; Cheikh Mbow; Monica Garcia; Stéphanie Horion; Inge Sandholt; Bo Holm‐Rasmussen; Frank M. Göttsche; Marc‐Etienne Ridler; et al. (Global Change Biology, 2015)
The Dahra field site in Senegal, West Africa, was established in 2002 to monitor ecosystem properties of semiarid savanna grassland and their responses to climatic and environmental change. This article describes the environment and the ecosystem properties of the site using a unique set of in situ data. The studied variables include hydroclimatic variables, species composition, albedo, normalized difference vegetation index ( NDVI ), hyperspectral characteristics (350–1800 nm), surface reflectance anisotropy, brightness temperature, fraction of absorbed photosynthetic active radiation ( FAPAR ), biomass, vegetation water content, and land‐atmosphere exchanges of carbon ( NEE ) and energy. The Dahra field site experiences a typical Sahelian climate and is covered by coexisting trees (~3% canopy cover) and grass species, characterizing large parts of the Sahel. This makes the site suitable for investigating relationships between ecosystem properties and hydroclimatic variables for semiarid savanna ecosystems of the region. There were strong interannual, seasonal and diurnal dynamics in NEE , with high values of ~−7.5 g C m −2 day −1 during the peak of the growing season. We found neither browning nor greening NDVI trends from 2002 to 2012. Interannual variation in species composition was strongly related to rainfall distribution. NDVI and FAPAR were strongly related to species composition, especially for years dominated by the species Zornia glochidiata . This influence was not observed in interannual variation in biomass and vegetation productivity, thus challenging dryland productivity models based on remote sensing. Surface reflectance anisotropy (350–1800 nm) at the peak of the growing season varied strongly depending on wavelength and viewing angle thereby having implications for the design of remotely sensed spectral vegetation indices covering different wavelength regions. The presented time series of in situ data have great potential for dryland dynamics studies, global climate change related research and evaluation and parameterization of remote sensing products and dynamic vegetation models.

Oocyte maturation in the sloth’s giant tick Amblyomma varium (Acari: Ixodidae) in an ecological context - Gustavo S. Sanches; Marcos R. André; Angelo P. do Prado; Silmara M. Allegretti; Rafael N. Remedio; Pablo H. Nunes; Rosangela Z. Machado; Gervásio H. Bechara; Maria I. Camargo-Mathias (Experimental and Applied Acarology, 2014)

Seasonal dynamics of autotrophic and heterotrophic plankton metabolism and P CO2 in a subarctic Greenland fjord - Mikael K. Sejr; Dorte Krause-Jensen; Tage Dalsgaard; Sergio Ruiz-Halpern; Carlos M. Duarte; Mathias Middelboe; Ronne N. Glud; Jørgen Bendtsen; Thorsten J. S. Balsby; Søren Rysgaard (Limnology and Oceanography, 2014)
We measured net planktonic community production (NCP), community respiration (CR), and gross primary production (GPP) in September, February, and May in a subarctic Greenland fjord influenced by glacial meltwater and terrestrial runoff. Potential controls of pelagic carbon cycling, including the role of terrestrial carbon, were investigated by relating surface‐water partial pressure of CO 2 (P CO2 ), NCP, GPP, and CR to physicochemical conditions, chlorophyll a (Chl a) concentration, phytoplankton production, inventories of particulate (POC) and dissolved organic carbon (DOC) and vertical flux of POC. The planktonic community was net heterotrophic in the photic zone in September (NCP 5 ‒21 ± 45 mmol O 2 m ‒2 d ‒1 ) and February (NCP 5 ‒17 mmol O 2 m ‒2 d ‒1 ) but net autotrophic during a developing spring bloom in May (NCP 5 129 ± 102 mmol O 2 m ‒2 d ‒1 ). In September, higher temperatures, shorter day lengths, and lower Chl a concentrations compared with May caused increased rates of CR, lower GPP rates, and net heterotrophy in the photic zone. The GPP required to exceed CR and where NCP becomes positive was low (in May: 1.58 ± 0.48 µ mol O 2 L ‒1 d ‒1 and September: 3.06 ± 0.82 µ mol O 2 L ‒1 d ‒1 ) and in the range of open ocean values, indicating that allochtonous carbon did not stimulate CR. The P CO2 in the surface water was below atmospheric levels (September average 25.0 ± 0.71 Pa, February 35.4 ± 0.40 Pa, and May 19.8 ± 1.21 Pa), rendering the ecosystem a sink of atmospheric CO 2 . NCP was identified as an important driver of surface P CO2 , with high rates of autotrophy and vertical export of POC reducing surface P CO2 during summer. In winter, net heterotrophy added CO 2 to the water column, but this postive effect on P CO2 was balanced by simultaneous cooling of the water column, which decreased P CO2 because of increased solubility of CO 2 . High autochthonous production implies a relatively limited influence of allochthonous carbon on pelagic carbon balance and CO 2 dynamics in the fjord.

Reconstructing past ecological networks: the reconfiguration of seed-dispersal interactions after megafaunal extinction - Mathias M. Pires; Mauro Galetti; Camila I. Donatti; Marco A. Pizo; Rodolfo Dirzo; Paulo R. Guimarães (Oecologia, 2014)

Within- and transgenerational effects of ocean acidification on life history of marine three-spined stickleback (Gasterosteus aculeatus) - Franziska M. Schade; Catriona Clemmesen; K. Mathias Wegner (Marine Biology, 2014)

Gray matter density in relation to different facets of verbal creativity - Andreas Fink; Karl Koschutnig; Lisa Hutterer; Elisabeth Steiner; Mathias Benedek; Bernhard Weber; Gernot Reishofer; Ilona Papousek; Elisabeth M. Weiss (Brain Structure and Function, 2014)

Sperm Bundles in the Seminal Vesicle of the Crematogaster victima (Smith) Adult Males (Hymenoptera: Formicidae) - C M Oliveira; J Moreira; L F Gomes; M I Camargo-Mathias; J Lino-Neto (Neotropical Entomology, 2014)

Conditional ablation of TYK2 in immunity to viral infection and tumor surveillance - Raimund M. Vielnascher; Eva Hainzl; Nicole R. Leitner; Michael Rammerstorfer; David Popp; Agnieszka Witalisz; Rita Rom; Marina Karaghiosoff; Thomas Kolbe; Simone Müller; Thomas Rülicke; Caroline Lassnig; et al. (Transgenic Research, 2014)

Walking Drosophila align with the e-vector of linearly polarized light through directed modulation of angular acceleration - Mariel M. Velez; Mathias F. Wernet; Damon A. Clark; Thomas R. Clandinin (Journal of Comparative Physiology A, 2014)

Nicht-photorealistische Darstellungen zur Präsentation und Kommunikation zur Innenraumnavigation - Mathias Jahnke; Jukka M. Krisp; Florian Fackler (KN - Journal of Cartography and Geographic Information, 2014)

Inhibition of tumour spheroid-induced prometastatic intravasation gates in the lymph endothelial cell barrier by carbamazepine: drug testing in a 3D model - Mathias Teichmann; Nicole Kretschy; Sabine Kopf; Kanokwan Jarukamjorn; Atanas G. Atanasov; Katharina Viola; Benedikt Giessrigl; Philipp Saiko; Thomas Szekeres; Wolfgang Mikulits; Verena M. Dirsch; Nicole Huttary; et al. (Archives of Toxicology, 2013)

In vitro characterisation of the anti-intravasative properties of the marine product heteronemin - Sabine Kopf; Katharina Viola; Atanas G. Atanasov; Kanokwan Jarukamjorn; Lucie Rarova; Nicole Kretschy; Mathias Teichmann; Caroline Vonach; Philipp Saiko; Benedikt Giessrigl; Nicole Huttary; Ingrid Raab; et al. (Archives of Toxicology, 2013)

Diggin′ on U(biquitin): A Novel Method for the Identification of Physiological E3 Ubiquitin Ligase Substrates - Carrie E. Rubel; Jonathan C. Schisler; Eric D. Hamlett; Robert M. DeKroon; Mathias Gautel; Oscar Alzate; Cam Patterson (Cell Biochemistry and Biophysics, 2013)

Interannual variability of net ecosystem productivity in forests is explained by carbon flux phenology in autumn - Chaoyang Wu; Jing M. Chen; T. Andrew Black; David T. Price; Werner A. Kurz; Ankur R. Desai; Alemu Gonsamo; Rachhpal S. Jassal; Christopher M. Gough; Gil Bohrer; Danilo Dragoni; Mathias Herbst; et al. (Global Ecology and Biogeography, 2013)
Aim To investigate the importance of autumn phenology in controlling interannual variability of forest net ecosystem productivity ( NEP ) and to derive new phenological metrics to explain the interannual variability of NEP . Location N orth A merica and E urope. Method Flux data from nine deciduous broadleaf forests ( DBF ) and 13 evergreen needleleaf forests ( ENF ) across N orth A merica and E urope (212 site‐years) were used to explore the relationships between the yearly anomalies of annual NEP and several carbon flux based phenological indicators, including the onset/end of the growing season, onset/end of the carbon uptake period, the spring lag (time interval between the onset of growing season and carbon uptake period) and the autumn lag (time interval between the end of the carbon uptake period and the growing season). Meteorological variables, including global shortwave radiation, air temperature, soil temperature, soil water content and precipitation, were also used to explain the phenological variations. Results We found that interannual variability of NEP can be largely explained by autumn phenology, i.e. the autumn lag. While variation in neither annual gross primary productivity ( GPP ) nor in annual ecosystem respiration ( R e ) alone could explain this variability, the negative relationship between annual NEP and autumn lag was due to a larger R e / GPP ratio in years with a prolonged autumn lag. For DBF sites, a longer autumn lag coincided with a significant decrease in annual GPP but showed no correlation with annual R e . However, annual GPP was insensitive to a longer autumn lag in ENF sites but annual R e increased significantly. Main conclusions These results demonstrate that autumn phenology plays a more direct role than spring phenology in regulating interannual variability of annual NEP . In particular, the importance of respiration may be potentially underestimated in deriving phenological indicators.

Xanthohumol attenuates tumour cell-mediated breaching of the lymphendothelial barrier and prevents intravasation and metastasis - Katharina Viola; Sabine Kopf; Lucie Rarova; Kanokwan Jarukamjorn; Nicole Kretschy; Mathias Teichmann; Caroline Vonach; Atanas G. Atanasov; Benedikt Giessrigl; Nicole Huttary; Ingrid Raab; Sigurd Krieger; et al. (Archives of Toxicology, 2013)

The role of soil surface water regimes and raindrop impact on hillslope soil erosion and nutrient losses - Juan An; Fenli Zheng; Mathias J. M. Römkens; Guifang Li; Qingsen Yang; Leilei Wen; Bin Wang (Natural Hazards, 2013)

Impulsivity, attention, memory, and decision-making among adolescent marijuana users - Donald M. Dougherty; Charles W. Mathias; Michael A. Dawes; R. Michael Furr; Nora E. Charles; Anthony Liguori; Erin E. Shannon; Ashley Acheson (Psychopharmacology, 2013)

Proteomic analysis of the Cyanophora paradoxa muroplast provides clues on early events in plastid endosymbiosis - Fabio Facchinelli; Mathias Pribil; Ulrike Oster; Nina J. Ebert; Debashish Bhattacharya; Dario Leister; Andreas P. M. Weber (Planta, 2013)

Genome-wide study identifies two loci associated with lung function decline in mild to moderate COPD - Nadia N. Hansel; Ingo Ruczinski; Nicholas Rafaels; Don D. Sin; Denise Daley; Alla Malinina; Lili Huang; Andrew Sandford; Tanda Murray; Yoonhee Kim; Candelaria Vergara; Susan R. Heckbert; et al. (Human Genetics, 2013)

Deep mitochondrial introgression and hybridization among ecologically divergent vole species - Cristiane Bastos‐Silveira; Sara M. Santos; Rita Monarca; Maria da Luz Mathias; Gerald Heckel (Molecular Ecology, 2012)
The completion of speciation is typically difficult to ascertain in rapidly diverging taxa but the amount of hybridization and gene flow in sympatry or parapatry contains important information about the level of reproductive isolation achieved. Here, we examined the progress in speciation between the Mediterranean ( M icrotus duodecimcostatus ) and the Lusitanian pine vole ( M. lusitanicus ), which are part of the most rapid radiation of species known in mammals. These two Iberian pine voles are classified as separate species because of differences in morphology and ecology, but relatively many ambiguous individuals can be found in sympatric conditions. Our phylogenetic analyses of rangewide data from the mitochondrial cytochrome b gene (mt DNA ) demonstrated high levels of diversity and a basal separation in two parapatric lineages. However, mt DNA affiliation was at odds with morphological classification or geographical distribution of the taxa. In contrast, statistical analyses of microsatellites (nuc DNA ) showed two clear genetic clusters in allopatry and sympatry generally matching morphological classification. This cytonuclear discordance over a large geographic area suggests historical introgression of mt DNA from M . duodecimcostatus to M . lusitanicus . There was statistical evidence for at least two recent hybrids in the sympatry zone but gene flow is apparently low given clear‐cut differences in nuc DNA . Our results indicate a relatively advanced speciation process in these Iberian pine voles without fully established reproductive isolation. This situation enables use of combined population genomic and experimental approaches for the separation of patterns and mechanisms in the ongoing explosive diversification of these and other A rvicoline rodents in the future.

Low temperature acclimation of photosynthetic capacity and leaf morphology in the context of phloem loading type - Matthew R. Dumlao; Anza Darehshouri; Christopher M. Cohu; Onno Muller; Jennifer Mathias; William W. Adams; Barbara Demmig-Adams (Photosynthesis Research, 2012)

Computational modeling of the human atrial anatomy and electrophysiology - Olaf Dössel; Martin W. Krueger; Frank M. Weber; Mathias Wilhelms; Gunnar Seemann (Medical & Biological Engineering & Computing, 2012)

Broad geographical distribution and high genetic diversity of shrew-borne Seewis hantavirus in Central Europe - Mathias Schlegel; Lukáš Radosa; Ulrike M. Rosenfeld; Sabrina Schmidt; Cornelia Triebenbacher; Paul-Walter Löhr; Dieter Fuchs; Marta Heroldová; Eva Jánová; Michal Stanko; Ladislav Mošanský; Jana Fričová; et al. (Virus Genes, 2012)

Generation of mice with a conditional Stat1 null allele - Barbara Wallner; Nicole R. Leitner; Raimund M. Vielnascher; Elisabeth Kernbauer; Thomas Kolbe; Marina Karaghiosoff; Thomas Rülicke; Thomas Decker; Mathias Müller (Transgenic Research, 2012)

A Critical Re-Examination of the Intraluminal Filament MCAO Model: Impact of External Carotid Artery Transection - Rebecca C. Trueman; David J. Harrison; Dominic M. Dwyer; Stephen B. Dunnett; Mathias Hoehn; Tracy D. Farr (Translational Stroke Research, 2011)

Time delay correction of the synchrogram for optimized detection of cardiorespiratory coordination - Muammar M. Kabir; David A. Saint; Eugene Nalivaiko; Derek Abbott; Mathias Baumert (Medical & Biological Engineering & Computing, 2011)

Quantification of Cardiorespiratory Interactions Based on Joint Symbolic Dynamics - Muammar M. Kabir; David A. Saint; Eugene Nalivaiko; Derek Abbott; Andreas Voss; Mathias Baumert (Annals of Biomedical Engineering, 2011)

Secretory process of salivary glands of female Amblyomma cajennense (Acari: Ixodidae) ticks fed on resistant rabbits - P. H. Nunes; G. H. Bechara; M. I. Camargo Mathias (Experimental and Applied Acarology, 2011)

Low-degree earth deformation from reprocessed GPS observations - Mathias Fritsche; R. Dietrich; A. Rülke; M. Rothacher; P. Steigenberger (GPS Solutions, 2010)

“Hot standards” for the thermoacidophilic archaeon Sulfolobus solfataricus - Melanie Zaparty; Dominik Esser; Susanne Gertig; Patrick Haferkamp; Theresa Kouril; Andrea Manica; Trong K. Pham; Julia Reimann; Kerstin Schreiber; Pawel Sierocinski; Daniela Teichmann; Marleen van Wolferen; et al. (Extremophiles, 2010)

Molecular insights into the colonization and chromosomal diversification of Madeiran house mice - D. W. FÖRSTER; İ. GÜNDÜZ; A. C. NUNES; S. GABRIEL; M. G. RAMALHINHO; M. L. MATHIAS; J. BRITTON‐DAVIDIAN; J. B. SEARLE (Molecular Ecology, 2009)
The colonization history of Madeiran house mice was investigated by analysing the complete mitochondrial (mt) D‐loop sequences of 156 mice from the island of Madeira and mainland Portugal, extending on previous studies. The numbers of mtDNA haplotypes from Madeira and mainland Portugal were substantially increased (17 and 14 new haplotypes respectively), and phylogenetic analysis confirmed the previously reported link between the Madeiran archipelago and northern Europe. Sequence analysis revealed the presence of four mtDNA lineages in mainland Portugal, of which one was particularly common and widespread (termed the ‘Portugal Main Clade’). There was no support for population bottlenecks during the formation of the six Robertsonian chromosome races on the island of Madeira, and D‐loop sequence variation was not found to be structured according to karyotype. The colonization time of the Madeiran archipelago by Mus musculus domesticus was approached using two molecular dating methods (mismatch distribution and Bayesian skyline plot). Time estimates based on D‐loop sequence variation at mainland sites (including previously published data from France and Turkey) were evaluated in the context of the zooarchaeological record of M. m. domesticus. A range of values for mutation rate (μ) and number of mouse generations per year was considered in these analyses because of the uncertainty surrounding these two parameters. The colonization of Portugal and Madeira by house mice is discussed in the context of the best‐supported parameter values. In keeping with recent studies, our results suggest that mutation rate estimates based on interspecific divergence lead to gross overestimates concerning the timing of recent within‐species events.

Ecological correlates of species richness and population abundance patterns in the amphibian communities from the Albertine Rift, East Africa - Mathias Behangana; Panta M. B. Kasoma; Luca Luiselli (Biodiversity and Conservation, 2009)

Nanotechnology approaches for gene transfer - Karin E. Lundin; Oscar E. Simonson; Pedro M. D. Moreno; Eman M. Zaghloul; Iulian I. Oprea; Mathias G. Svahn; C. I. Edvard Smith (Genetica, 2009)

Structural model of the CopA copper ATPase of Enterococcus hirae based on chemical cross-linking - Mathias Lübben; Reto Portmann; Gerd Kock; Raphael Stoll; Malin M. Young; Marc Solioz (BioMetals, 2009)

Effects of ultra-marathon on circulating DNA and mRNA expression of pro- and anti-apoptotic genes in mononuclear cells - Johanna Atamaniuk; Karl M. Stuhlmeier; Claudia Vidotto; Harald Tschan; Astrid Dossenbach-Glaninger; Mathias M. Mueller (European Journal of Applied Physiology, 2008)

Morphological changes in the salivary glands of Amblyomma cajennense females (Acari: Ixodidae) in different feeding stages on rabbits at first infestation - P. H. Nunes; G. H. Bechara; M. I. Camargo-Mathias (Experimental and Applied Acarology, 2008)

Comparison of 50- and 100-g l-tryptophan depletion and loading formulations for altering 5-HT synthesis: pharmacokinetics, side effects, and mood states - Donald M. Dougherty; Dawn M. Marsh-Richard; Charles W. Mathias; Ashley J. Hood; Merideth A. Addicott; F. Gerard Moeller; Christopher J. Morgan; Abdulla A.-B. Badawy (Psychopharmacology, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

The effects of alcohol on laboratory-measured impulsivity after l-Tryptophan depletion or loading - Donald M. Dougherty; Dawn M. Marsh; Charles W. Mathias; Michael A. Dawes; Don M. Bradley; Chris J. Morgan; Abdulla A.-B. Badawy (Psychopharmacology, 2007)

Regulation of cardiac inwardly rectifying potassium current IK1 and Kir2.x channels by endothelin-1 - Claudia Kiesecker; Edgar Zitron; Daniel Scherer; Sonja Lueck; Ramona Bloehs; Eberhard P. Scholz; Marcus Pirot; Sven Kathöfer; Dierk Thomas; Volker A. W. Kreye; Johann Kiehn; Mathias M. Borst; et al. (Journal of Molecular Medicine, 2006)

SNEP: SNP-derived Epitope Prediction program for minor H antigens - Mathias M. Schuler; Pierre Dönnes; Maria-Dorothea Nastke; Oliver Kohlbacher; Hans-Georg Rammensee; Stefan Stevanovic (Immunogenetics, 2005)

Light Measurement Methods Related to Forage Yield in a Grazed Northern Conifer Silvopasture in the Appalachian Region of Eastern USA - C. M. Feldhake; J. P. S. Neel; D. P. Belesky; E. L. Mathias (Agroforestry Systems, 2005)

Influence of physical environmental characteristics and anthropogenic factors on the position and structure of a contact zone between two chromosomal races of the house mouse on the island of Madeira (North Atlantic, Portugal) - A. C. Nunes; J. Britton‐Davidian; J. Catalan; M. G. Ramalhinho; R. Capela; M. L. Mathias; G. Ganem (Journal of Biogeography, 2005)
Aim This study aimed to investigate if and how environmental characteristics (physical factors of the natural environment and the human impact on the landscape) influence the position and structure of a contact zone between two chromosomal races of the house mouse ( Mus musculus domesticus Rutty 1712) from the island of Madeira. Location The western part of Madeira, a volcanic island in the North Atlantic. Methods Mice were sampled along a south/north‐western transect following the main road, in human‐modified outdoor habitats. Karyotypes of mice were determined using the yeast‐stimulated bone marrow cell method. Trapping sites were characterized in terms of their physical (altitude, temperature, precipitation and soil type) and habitat (human landscape use and occupancy) features. Demographic parameters of mouse populations, based on trapping‐with‐removal techniques, were also analysed (relative abundance, sex‐ratio, juvenile ratio and female fertility ratio), as well as body size (weight and length). Results Four chromosomal zones were identified on the basis of the frequency of two diagnostic rearrangements (Rb(6.7) in race E. Calheta and Rb(7.15) in race A. Cruz). E. Calheta was present in the two southern‐most zones, followed by the contact zone characterized by the presence of two inter‐racial hybrids and the co‐occurrence of mice belonging to the two races. The northern‐most part of the transect was occupied by A. Cruz. Environmental features differed leading us to split the transect into two parts. The southern part is characterized by lower altitude and precipitation, milder temperature, better soil quality supporting vegetable crops and vineyards, and more abundant and evenly distributed human habitats. This southern part is occupied by E. Calheta mice. The north‐western part presents characteristics opposite to those described above with cereals as the main cultivated crop, and it includes the contact zone as well as the zone inhabited by A. Cruz mice. The demographic parameters evaluated in this study did not differ significantly between chromosomal zones. Main conclusions This ecological survey highlights differences in climatic and edaphic features that have moulded the agricultural activities of humans, contributing to a differentiation of their spatial development, and hence the structure of potential habitats for mice. Results are interpreted within the source–sink framework of population dynamics, following which E. Calheta may function as a source and the areas where A. Cruz and the contact zone are located may function as a sink. Our study suggests that the position and chromosomal composition of the contact zone is influenced by the human component underlying broader environmental features. Similar characteristics were most likely present during the historical settlement of Madeira. They may have favoured the independent divergence of the two races and influenced the dynamics of the contact zone.

Regulation of protein kinase C isozymes in volume overload cardiac hypertrophy - Martin U. Braun; Paul LaRosée; Gregor Simonis; Mathias M. Borst; Ruth H. Strasser (Molecular and Cellular Biochemistry, 2004)

Infrastruktur-Consulting: Der Verkehrslandeplatz Rgen - Mathias M. Lehmann (Standort, 2004)

Erratum to: DNA strand breaks, oxidative damage, and 1-OH pyrene in roofers with coal-tar pitch dust and/or asphalt fume exposure - Mark Toraason; Charles Hayden; Dave Marlow; Richard Rinehart; Patty Mathias; Dwight Werren; Gayle D. DeBord; Thomas M. Reid (International Archives of Occupational and Environmental Health, 2002)

Developmental Instability in a Riparian Population of the Algerian Mouse(Mus spretus) Associated with a Heavy Metal–Polluted Area in Central Portugal - A. C. Nunes; J.-C. Auffray; M. L. Mathias (Archives of Environmental Contamination and Toxicology, 2001)

DNA strand breaks, oxidative damage, and 1-OH pyrene in roofers with coal-tar pitch dust and/or asphalt fume exposure - Mark Toraason; Charles Hayden; Dave Marlow; Richard Rinehart; Patty Mathias; Dwight Werren; D. Gayle DeBord; Thomas M. Reid (International Archives of Occupational and Environmental Health, 2001)

Molecular studies on the colonization of the Madeiran archipelago by house mice - İ. GÜndüz; J.‐C. Auffray; J. Britton‐Davidian; J. Catalan; G. Ganem; M. G. Ramalhinho; M. L. Mathias; J. B. Searle (Molecular Ecology, 2001)
To study the colonization history of the house mouse ( Mus musculus domesticus ) on the Madeiran archipelago, complete mitochondrial D‐ loop sequences were obtained for 44 individuals from Madeira, Porto Santo and Ilhas Desertas. Altogether, 19 D‐ loop haplotypes were identified which formed part of a single clade in a phylogeny incorporating haplotypes from elsewhere in the range of M. m. domesticus , indicating that the Madeiras were colonized from a single source. Similarities between the sequences found in the Madeiras and those in Scandinavia and northern Germany suggest that northern Europe was the source area, and there is the intriguing possibility that the Vikings may have accidentally brought house mice to the archipelago. However, there is no record of Vikings visiting the Madeiras; on historical grounds, Portugal is the most likely source area for Madeiran mice and further molecular data from Portugal are needed to rule out that possibility.

The theory of organism and the culturalist foundation of biology - Mathias Gutmann; Eva M. Neumann-Held (Theory in Biosciences, 2000)

Guest-editorial: “Organism” — Historical and philosophical issues - Mathias Gutmann; Eva M. Neumann-Held; Christoph Rehmann-Sutter (Theory in Biosciences, 2000)

Cell therapy using microencapsulated 293 cells transfected with a gene construct expressing CYP2B1, an ifosfamide converting enzyme, instilled intra-arterially in patients with advanced-stage pancreatic carcinoma: a phase I/II study - M. Löhr; Zoltan Tibor Bago; Helga Bergmeister; Manfred Ceijna; Mathias Freund; Wolfgang Gelbmann; Walter H. Günzburg; Ralf Jesnowski; Johannes Hain; Karlheinz Hauenstein; Wolfgang Henninger; Anne Hoffmeyer; et al. (Journal of Molecular Medicine, 1999)

Engineering of betabellin 15D: Copper(II)-induced folding of a fibrillar β-sandwich protein - Amareth Lim; Philippe A. Guy; Alexander M. Makhov; Matthew J. Saderholm; Mathias Kroll; Yibing Yan; Robert J. Anderegg; Jack D. Griffith; Bruce W. Erickson (International Journal of Peptide Research and Therapeutics, 1999)

Visualization of the Brassica self-incompatibility S-locus on identified oilseed rape chromosomes - Yasuko Kamisugi; Shigeki Nakayama; Carmel M. O'Neil; Raymond J. Mathias; Martin Trick; Kiichi Fukui (Plant Molecular Biology, 1998)

A six-module human nebulin fragment bundles actin filaments and induces actin polymerization - S. M. Gonsior; Mathias Gautel; Horst Hinssen (Journal of Muscle Research and Cell Motility, 1998)

Somatic embryogenesis and plant regeneration from stem explants of Moricandia arvensis - W. Craig; A. Wiegand; C. M. O'Neill; R. J. Mathias; J. B. Power; M. R. Davey (Plant Cell Reports, 1997)

s 59th annual meeting Potato Association of America - D. E. Hudson; M. D. Volz; B. B. DePhillips; Gene A. Mathia; Frank Haynes; N. A. Wynn; Allen E. Abrahams; Lewis A. Schaper; Paul H. Orr; Earl C. Yaeger; Combs Joseph; Robert L. Mercer; et al. (American Journal of Potato Research, 1975)